Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease. - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea-Teodor; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon λ2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing. and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing. ). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging. IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD. BACKGROUND & AIMS RESULTS METHODS CONCLUSIONS
Keywords: Crohn’s Disease; Interferon λ; Ulcerative Colitis; Wound Healing

Activation of Epithelial Signal Transducer and Activator of Transcription 1 by Interleukin 28 Controls Mucosal Healing in Mice With Colitis and Is Increased in Mucosa of Patients With Inflammatory Bowel Disease - Chiriac, Mircea T.; Buchen, Barbara; Wandersee, Alexandra; Hundorfean, Gheorghe; Günther, Claudia; Bourjau, Yvonne; Doyle, Sean E.; Frey, Benjamin; Ekici, Arif Bülent; Büttner, Christian; Weigmann, Benno; Atreya, Raja; et al. (Gastroenterology, 2017)
We investigated the roles of interleukin 28A (also called IL28A or interferon ?2) in intestinal epithelial cell (IEC) activation, studying its effects in mouse models of inflammatory bowel diseases (IBD) and intestinal mucosal healing.Colitis was induced in C57BL/6JCrl mice (controls), mice with IEC-specific disruption of Stat1 (Stat1IEC-KO), mice with disruption of the interferon ? receptor 1 gene (Il28ra(-/-)), and mice with disruption of the interferon regulatory factor 3 gene (Irf3(-/-)), with or without disruption of Irf7 (Irf7(-/-)). We used high-resolution mini-endoscopy and in vivo imaging methods to assess colitis progression. We used 3-dimensional small intestine and colon organoids, along with RNA-Seq and gene ontology methods, to characterize the effects of IL28 on primary IECs. We studied the effects of IL28 on the human intestinal cancer cell line Caco-2 in a wound-healing assay, and in mice colon wounds. Colonic biopsies and resected tissue from patients with IBD (n = 62) and patients without colon inflammation (controls, n = 23) were analyzed by quantitative polymerase chain rection to measure expression of IL28A, IL28RA, and other related cytokines; biopsy samples were also analyzed by immunofluorescence to identify sources of IL28 production. IECs were isolated from patient tissues and incubated with IL28; signal transducer and activator of transcription 1 (STAT1) phosphorylation was measured by immunoblots and confocal imaging.Lamina propria cells in colon tissues of patients with IBD, and mice with colitis, had increased expression of IL28 compared with controls; levels of IL28R were increased in the colonic epithelium of patients with IBD and mice with colitis. Administration of IL28 induced phosphorylation of STAT1 in primary human and mouse IECs, increasing with dose. Il28ra(-/-), Irf3(-/-), Irf3(-/-)Irf7(-/-), as well as Stat1IEC-KO mice, developed more severe colitis after administration of dextran sulfate sodium than control mice, with reduced epithelial restitution. Il28ra(-/-) and Stat1IEC-KO mice also developed more severe colitis in response to oxazolone than control mice. We found IL28 to induce phosphorylation (activation) of STAT1 in epithelial cells, leading to their proliferation in organoid culture. Administration of IL28 to mice with induced colonic wounds promoted mucosal healing.IL28 controls proliferation of IECs in mice with colitis and accelerates mucosal healing by activating STAT1. IL28 might be developed as a therapeutic agent for patients with IBD.
EVALuna2:9356

Activation of intestinal epithelial Stat3 orchestrates tissue defense during gastrointestinal infection - Wittkopf, Nadine; Pickert, Geethanjali; Billmeier, Ulrike; Mahapatro, Mousumi; Wirtz, Stefan; Martini, Eva; Leppkes, Moritz; Neurath, Markus; Becker, Christoph (PLoS ONE, 2015)
Gastrointestinal infections with EHEC and EPEC are responsible for outbreaks of diarrheal diseases and represent a global health problem. Innate first-line-defense mechanisms such as production of mucus and antimicrobial peptides by intestinal epithelial cells are of utmost importance for host control of gastrointestinal infections. For the first time, we directly demonstrate a critical role for Stat3 activation in intestinal epithelial cells upon infection of mice with Citrobacter rodentium - a murine pathogen that mimics human infections with attaching and effacing Escherichia coli. C. rodentium induced transcription of IL-6 and IL-22 in gut samples of mice and was associated with activation of the transcription factor Stat3 in intestinal epithelial cells. C. rodentium infection induced expression of several antimicrobial peptides such as RegIII? and Pla2g2a in the intestine which was critically dependent on Stat3 activation. Consequently, mice with specific deletion of Stat3 in intestinal epithelial cells showed increased susceptibility to C. rodentium infection as indicated by high bacterial load, severe gut inflammation, pronounced intestinal epithelial cell death and dissemination of bacteria to distant organs. Together, our data implicate an essential role for Stat3 activation in intestinal epithelial cells during C. rodentium infection. Stat3 concerts the host response to bacterial infection by controlling bacterial growth and suppression of apoptosis to maintain intestinal epithelial barrier function.
EVALuna2:1990

Alzheimer’s disease-related presenilins are key to intestinal epithelial cell function and gut immune homoeostasis - Erkert, Lena; Gamez-Belmonte, Reyes; Kabisch, Melanie; Schödel, Lena; Patankar, Jay; Gonzalez Acera, Miguel; Mahapatro, Mousumi; Bao, Lili; Plattner, Christina; Kühl, Anja A.; Shen, Jie; Serneels, Lutgarde; et al. (Gut, 2024)
Objective Mutations in presenilin genes are the major cause of Alzheimer’s disease. However, little is known about their expression and function in the gut. In this study, we identify the presenilins Psen1 and Psen2 as key molecules that maintain intestinal homoeostasis. Design Human inflammatory bowel disease (IBD) and control samples were analysed for Psen1 expression. Newly generated intestinal epithelium-specific Psen1-deficient, Psen2-deficient and inducible Psen1/Psen2 double-deficient mice were used to dissect the functional role of presenilins in intestinal homoeostasis. Results Psen1 expression was regulated in experimental gut inflammation and in patients with IBD. Induced deletion of Psen1 and Psen2 in mice caused rapid weight loss and spontaneous development of intestinal inflammation. Mice exhibited epithelial barrier disruption with bacterial translocation and deregulation of key pathways for nutrient uptake. Wasting disease was independent of gut inflammation and dysbiosis, as depletion of microbiota rescued Psen-deficient animals from spontaneous colitis development but not from weight loss. On a molecular level, intestinal epithelial cells lacking Psen showed impaired Notch signalling and dysregulated epithelial differentiation. Conclusion Overall, our study provides evidence that Psen1 and Psen2 are important guardians of intestinal homoeostasis and future targets for barrier-promoting therapeutic strategies in IBD.
CRIS-Team Scopus Importer:2024-08-30

Analysis of the interferon-γ-induced secretome of intestinal endothelial cells: putative impact on epithelial barrier dysfunction in IBD - Naschberger, Elisabeth; Flierl, Christian; Huang, Jinghao; Erkert, Lena; Gámez Belmonte, Maria de los Reyes; Gonzalez Acera, Miguel; Bober, Magdalena; Mehnert, Martin; Becker, Christoph; Schellerer, Vera S.; Britzen-Laurent, Nathalie; Stürzl, Michael (Frontiers in Cell and Developmental Biology, 2023)
The development of inflammatory bowel diseases (IBD) involves the breakdown of two barriers: the epithelial barrier and the gut-vascular barrier (GVB). The destabilization of each barrier can promote initiation and progression of the disease. Interestingly, first evidence is available that both barriers are communicating through secreted factors that may accordingly serve as targets for therapeutic modulation of barrier functions. Interferon (IFN)-γ is among the major pathogenesis factors in IBD and can severely impair both barriers. In order to identify factors transmitting signals from the GVB to the epithelial cell barrier, we analyzed the secretome of IFN-γ-treated human intestinal endothelial cells (HIEC). To this goal, HIEC were isolated in high purity from normal colon tissues. HIEC were either untreated or stimulated with IFN-γ (10 U/mL). After 48 h, conditioned media (CM) were harvested and subjected to comparative hyper reaction monitoring mass spectrometry (HRM™ MS). In total, 1,084 human proteins were detected in the HIEC-CM. Among these, 43 proteins were present in significantly different concentrations between the CM of IFN-γ- and control-stimulated HIEC. Several of these proteins were also differentially expressed in various murine colitis models as compared to healthy animals supporting the relevance of these proteins secreted by inflammatory activated HIEC in the inter-barrier communication in IBD. The angiocrine pathogenic impact of these differentially secreted HIEC proteins on the epithelial cell barrier and their perspectives as targets to treat IBD by modulation of trans-barrier communication is discussed in detail.
CRIS-Team Scopus Importer:2023-09-08
Keywords: angiocrine; barrier; cytokines; endothelial; IBD-inflammatory bowel disease; interferon; paracrine; secretion

An IFN-STAT1-MLKL axis drives programmed necrosis of Paneth cells in Crohn's ileitis - Hartmann, Leonie; Siegmund, B.; Weidinger, C.; Becker, Christoph; Neurath, Markus; Günther, Claudia (JOURNAL OF CROHNS & COLITIS, 2020)
CRIS-Team WoS Importer:2020-04-10

Anti-TNF Antibodies and Autophagy: A Hidden Nexus for a Successful Therapeutic Response? - Genua, Marco; Becker, Christoph; Vetrano, Stefania (Journal of Crohns & Colitis, 2016)
EVALuna2:2104

Apoptosis, necrosis and necroptosis: cell death regulation in the intestinal epithelium. - Günther, Claudia; Neumann, Helmut; Neurath, Markus; Becker, Christoph (Gut, 2013)
Intestinal epithelial cells (IEC) are organised as a single cell layer which covers the intestine. Their primary task is to absorb nutrients present in the intestinal lumen. However, IEC also play an important role in the immune defence of our body by building a barrier that separates the bowel wall from potentially hazardous bacteria present in the gut lumen. The life cycle of IEC is determined by the time span in which cells migrate from their place of origin at the crypt base to the villus tip, from where they are shed into the lumen. Cell death in the intestinal epithelium has to be tightly regulated and irregularities might cause pathologies. Excessive cell death has been associated with chronic inflammation as seen in patients with Crohn's disease and ulcerative colitis. While until recently apoptosis was discussed as being essential for epithelial turnover and tissue homeostasis in the intestinal epithelium, recent data using gene deficient mice have challenged this concept. Moreover, an apoptosis-independent mode of programmed cell death, termed necroptosis, has been identified and described in the intestinal epithelium. The following article reviews previous studies on cell death regulation in IEC and a potential role of necroptosis for gut homeostasis.
Keywords: Cell death; Paneth cells; RIP; bacterial translocation; caspase-8; cytokines; endoscopy; epithelial cells; gene expression; inflammatory bowel disease; necroptosis; signal transduction

Apoptosis, necrosis and necroptosis: cell death regulation in the intestinal epithelium. - Günther, Claudia; Neumann, Helmut; Neurath, Markus; Becker, Christoph (Gut, 2013)
Intestinal epithelial cells (IEC) are organised as a single cell layer which covers the intestine. Their primary task is to absorb nutrients present in the intestinal lumen. However, IEC also play an important role in the immune defence of our body by building a barrier that separates the bowel wall from potentially hazardous bacteria present in the gut lumen. The life cycle of IEC is determined by the time span in which cells migrate from their place of origin at the crypt base to the villus tip, from where they are shed into the lumen. Cell death in the intestinal epithelium has to be tightly regulated and irregularities might cause pathologies. Excessive cell death has been associated with chronic inflammation as seen in patients with Crohn's disease and ulcerative colitis. While until recently apoptosis was discussed as being essential for epithelial turnover and tissue homeostasis in the intestinal epithelium, recent data using gene deficient mice have challenged this concept. Moreover, an apoptosis-independent mode of programmed cell death, termed necroptosis, has been identified and described in the intestinal epithelium. The following article reviews previous studies on cell death regulation in IEC and a potential role of necroptosis for gut homeostasis.
Keywords: Cell death; Paneth cells; RIP; bacterial translocation; caspase-8; cytokines; endoscopy; epithelial cells; gene expression; inflammatory bowel disease; necroptosis; signal transduction.

Apoptotic cell death in disease—Current understanding of the NCCD 2023 - Vitale, Ilio; Pietrocola, Federico; Guilbaud, Emma; Aaronson, Stuart A.; Abrams, John M.; Adam, Dieter; Agostini, Massimiliano; Agostinis, Patrizia; Alnemri, Emad S.; Altucci, Lucia; Amelio, Ivano; Andrews, David W.; et al. (Cell Death and Differentiation, 2023)
Apoptosis is a form of regulated cell death (RCD) that involves proteases of the caspase family. Pharmacological and genetic strategies that experimentally inhibit or delay apoptosis in mammalian systems have elucidated the key contribution of this process not only to (post-)embryonic development and adult tissue homeostasis, but also to the etiology of multiple human disorders. Consistent with this notion, while defects in the molecular machinery for apoptotic cell death impair organismal development and promote oncogenesis, the unwarranted activation of apoptosis promotes cell loss and tissue damage in the context of various neurological, cardiovascular, renal, hepatic, infectious, neoplastic and inflammatory conditions. Here, the Nomenclature Committee on Cell Death (NCCD) gathered to critically summarize an abundant pre-clinical literature mechanistically linking the core apoptotic apparatus to organismal homeostasis in the context of disease.
CRIS-Team Scopus Importer:2023-05-05

Assessment of tumor development and wound healing using endoscopic techniques in mice - Günther, Claudia; Neurath, Markus; Waldner, Maximilian; Neufert, Clemens; Wirtz, Stefan; Becker, Christoph; et al. (Gastroenterology, 2010)
Mouse models of intestinal inflammation and colon cancer are valuable tools to gain insights into the pathogenesis of the corresponding human diseases. Recently, in vivo mouse endoscopy has been developed, allowing not only the high-resolution monitoring and scoring of experimental disease development, but also enables the investigator to perform manipulations, including local injection of reagents or the taking of biopsies for molecular and histopathologic analyses. Chromoendoscopic staining with methylene blue enables visualization of the crypt structure and allows discrimination between inflammatory and neoplastic changes. The development of endoscopic techniques in live mice opened new options for the investigation of disease mechanisms in the gut and for the preclinical testing of potential therapeutic effects of drug candidates. Finally, mouse endoscopy can help to reduce animal numbers needed to gain significant experimental data.

At the Forefront of the Mucosal Barrier: The Role of Macrophages in the Intestine - Ruder, Barbara; Becker, Christoph (Cells, 2020)
Macrophages are part of the innate immunity and are key players for the maintenance of intestinal homeostasis. They belong to the group of mononuclear phagocytes, which exert bactericidal functions and help to clear apoptotic cells. Moreover, they play essential roles for the maintenance of epithelial integrity and tissue remodeling during wound healing processes and might be implicated in intestinal tumor development. Macrophages are antigen-presenting cells and secrete immune-modulatory factors, like chemokines and cytokines, which are necessary to activate other intestinal immune cells and therefore to shape immune responses in the gut. However, overwhelming activation or increased secretion of pro-inflammatory cytokines might also contribute to the pathogenesis of inflammatory bowel disease. Presently, intestinal macrophages are in the center of intense studies, which might help to develop new therapeutic strategies to counteract the development or treat already existing inflammatory diseases in the gut. In this review, we focus on the origin of intestinal macrophages and, based on current knowledge, discuss their role in the gut during homeostasis and inflammation, as well as during intestinal wound healing and tumor development.
CRIS-Team Scopus Importer:2020-10-16
Keywords: IBD; inflammation; intestine; macrophages; phagocytosis

Autophagy in cancer therapy—molecular mechanisms and current clinical advances - Ganzleben, Ingo; Neurath, Markus; Becker, Christoph (Cancers, 2021)
Autophagy is a crucial general survival tactic of mammalian cells. It describes the capability of cells to disassemble and partially recycle cellular components (e.g., mitochondria) in case they are damaged and pose a risk to cell survival or simply if their resources are urgently needed elsewhere at the time. Autophagy-associated pathomechanisms have been increasingly recognized as important disease mechanisms in non-malignant (neurodegeneration, diffuse parenchymal lung disease) and malignant conditions alike. However, the overall consequences of autophagy for the organism depend particularly on the greater context in which autophagy occurs, such as the cell type or whether the cell is proliferating. In cancer, autophagy sustains cancer cell survival under challenging, i.e., resource-depleted, conditions. However, this leads to situations in which cancer cells are completely dependent on autophagy. Accordingly, autophagy represents a promising yet complex target in cancer treatment with therapeutically induced increase and decrease of autophagic flux as important therapeutic principles.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Autophagy; Cancer; Glutamine; Hydroxychloroquine; Mitophagy; Reverse Warburg effect

Breaking bad: necroptosis in the pathogenesis of gastrointestinal diseases - Patankar, Jay; Bubeck, Marvin; Gonzalez Acera, Miguel; Becker, Christoph (Frontiers in Immunology, 2023)
A delicate balance between programmed cell death and proliferation of intestinal epithelial cells (IEC) exists in the gut to maintain homeostasis. Homeostatic cell death programs such as anoikis and apoptosis ensure the replacement of dead epithelia without overt immune activation. In infectious and chronic inflammatory diseases of the gut, this balance is invariably disturbed by increased levels of pathologic cell death. Pathological forms of cell death such as necroptosis trigger immune activation barrier dysfunction, and perpetuation of inflammation. A leaky and inflamed gut can thus become a cause of persistent low-grade inflammation and cell death in other organs of the gastrointestinal (GI) tract, such as the liver and the pancreas. In this review, we focus on the advances in the molecular and cellular understanding of programmed necrosis (necroptosis) in tissues of the GI tract. In this review, we will first introduce the reader to the basic molecular aspects of the necroptosis machinery and discuss the pathways leading to necroptosis in the GI system. We then highlight the clinical significance of the preclinical findings and finally evaluate the different therapeutic approaches that attempt to target necroptosis against various GI diseases. Finally, we review the recent advances in understanding the biological functions of the molecules involved in necroptosis and the potential side effects that may occur due to their systemic inhibition. This review is intended to introduce the reader to the core concepts of pathological necroptotic cell death, the signaling pathways involved, its immuno-pathological implications, and its relevance to GI diseases. Further advances in our ability to control the extent of pathological necroptosis will provide better therapeutic opportunities against currently intractable GI and other diseases.
CRIS-Team Scopus Importer:2023-08-25
Keywords: caspase 8; inflammatory bowel disease; MLKL; necroptosis; RIPK3; therapeutic

Caspase-8 controls the gut response to microbial challenges by Tnf-?-dependent and independent pathways - Günther, Claudia; Buchen, Barbara; He, Gui-Wei; Hornef, Mathias; Torow, Natalia; Neumann, Helmut; Wittkopf, Nadine; Martini, Eva; Basic, Marijana; Bleich, Andre; Watson, Alastair J. M.; Neurath, Markus; et al. (Gut, 2015)
Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear.We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo.TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-? and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-?.Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies.
EVALuna2:1993

Caspase-8 controls the gut response to microbial challenges by Tnf-α-dependent and independent pathways. - Günther, Claudia; Buchen, Barbara; He, Guiwei; Hornef, Mathias W.; Torow, Natalia; Neumann, Helmut; Martini, Eva; Basic, Marijana; Bleich, André; Watson, Alastair J.M.; Neurath, Markus; Becker, Christoph; et al. (Gut, 2015)
Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies. TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-α and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-α. Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear. We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo. CONCLUSIONS RESULTS OBJECTIVES DESIGN
Keywords: Apoptosis; Cell Biology; Cell Death; Intestinal Epithelium; TNF

Caspase-8 controls the gut response to microbial challenges by Tnf-α-dependent and independent pathways - Günther, Claudia; Buchen, Barbara; Hornef, Mathias; Torow, Natalia; Neumann, Helmut; Martini, Eva; Basic, Marijana; Bleich, Andre; Watson, Alastair; Neurath, Markus; Becker, Christoph; et al. (Gut, 2015)
Together, our data demonstrate an essential role for caspase-8 in maintaining the gut barrier in response to mucosal pathogens by permitting inflammatory shedding and preventing necroptosis of infected cells. These data suggest that therapeutic strategies targeting the cell death machinery represent a promising new option for the treatment of inflammatory and infective enteropathies. TLR stimulation of IEC was associated with a rapid activation of caspase-8 and increased epithelial cell shedding. In mice with an epithelial cell-specific deletion of caspase-8 TLR stimulation caused Rip3-dependent epithelial necroptosis instead of apoptosis. Mortality and tissue damage were more severe in mice in which IECs died by necroptosis than apoptosis. Inhibition of receptor-interacting protein (Rip) kinases rescued the epithelium from TLR-induced gut damage. TLR3-induced necroptosis was directly mediated via TRIF-dependent pathways, independent of Tnf-α and type III interferons, whereas TLR4-induced tissue damage was critically dependent on Tnf-α. Intestinal epithelial cells (IEC) express toll-like receptors (TLR) that facilitate microbial recognition. Stimulation of TLR ligands induces a transient increase in epithelial cell shedding, a mechanism that serves the antibacterial and antiviral host defence of the epithelium and promotes elimination of intracellular pathogens. Although activation of the extrinsic apoptosis pathway has been described during inflammatory shedding, its functional involvement is currently unclear. We investigated the functional involvement of caspase-8 signalling in microbial-induced intestinal cell shedding by injecting Lipopolysaccharide (LPS) to mimic bacterial pathogens and poly(I:C) as a probe for RNA viruses in vivo. CONCLUSIONS RESULTS OBJECTIVES DESIGN
Keywords: Apoptosis; Cell Biology; Cell Death; Intestinal Epithelium; TNF

Caspase-8 in endothelial cells maintains gut homeostasis and prevents small bowel inflammation in mice - Tisch, Nathalie; Mogler, Carolin; Stojanovic, Ana; Luck, Robert; Korhonen, Emilia A.; Ellerkmann, Alexander; Adler, Heike; Singhal, Mahak; Schermann, Geza; Erkert, Lena; Patankar, Jay; Karakatsani, Andromachi; et al. (Embo Molecular Medicine, 2022)
The gut has a specific vascular barrier that controls trafficking of antigens and microbiota into the bloodstream. However, the molecular mechanisms regulating the maintenance of this vascular barrier remain elusive. Here, we identified Caspase-8 as a pro-survival factor in mature intestinal endothelial cells that is required to actively maintain vascular homeostasis in the small intestine in an organ-specific manner. In particular, we find that deletion of Caspase-8 in endothelial cells results in small intestinal hemorrhages and bowel inflammation, while all other organs remained unaffected. We also show that Caspase-8 seems to be particularly needed in lymphatic endothelial cells to maintain gut homeostasis. Our work demonstrates that endothelial cell dysfunction, leading to the breakdown of the gut-vascular barrier, is an active driver of chronic small intestinal inflammation, highlighting the role of the intestinal vasculature as a safeguard of organ function.
CRIS-Team Scopus Importer:2022-05-13
Keywords: caspase-8; chronic intestinal inflammation; endothelium; necroptosis; vascular homeostasis

Caspase-8 regulates TNF-α-induced epithelial necroptosis and terminal ileitis - Günther, Claudia; Martini, Eva; Amann, Kerstin Ute; Weigmann, Benno; Neumann, Helmut; Waldner, Maximilian; Tenzer, Stefan; Neurath, Markus; Becker, Christoph; et al. (Nature, 2011)
Dysfunction of the intestinal epithelium is believed to result in the excessive translocation of commensal bacteria into the bowel wall that drives chronic mucosal inflammation in Crohn's disease, an incurable inflammatory bowel disease in humans characterized by inflammation of the terminal ileum. In healthy individuals, the intestinal epithelium maintains a physical barrier, established by the tight contact of cells. Moreover, specialized epithelial cells such as Paneth cells and goblet cells provide innate immune defence functions by secreting mucus and antimicrobial peptides, which hamper access and survival of bacteria adjacent to the epithelium. Epithelial cell death is a hallmark of intestinal inflammation and has been discussed as a possible pathogenic mechanism driving Crohn's disease in humans. However, the regulation of epithelial cell death and its role in intestinal homeostasis remain poorly understood. Here we demonstrate a critical role for caspase-8 in regulating necroptosis of intestinal epithelial cells (IECs) and terminal ileitis. Mice with a conditional deletion of caspase-8 in the intestinal epithelium (Casp8(ΔIEC)) spontaneously developed inflammatory lesions in the terminal ileum and were highly susceptible to colitis. Casp8(ΔIEC) mice lacked Paneth cells and showed reduced numbers of goblet cells, indicating dysregulated antimicrobial immune cell functions of the intestinal epithelium. Casp8(ΔIEC) mice showed increased cell death in the Paneth cell area of small intestinal crypts. Epithelial cell death was induced by tumour necrosis factor (TNF)-α, was associated with increased expression of receptor-interacting protein 3 (Rip3; also known as Ripk3) and could be inhibited on blockade of necroptosis. Lastly, we identified high levels of RIP3 in human Paneth cells and increased necroptosis in the terminal ileum of patients with Crohn's disease, suggesting a potential role of necroptosis in the pathogenesis of this disease. Together, our data demonstrate a critical function of caspase-8 in regulating intestinal homeostasis and in protecting IECs from TNF-α-induced necroptotic cell death.

CCR8 Signaling via CCL1 Regulates Responses of Intestinal IFN-γ Producing Innate Lymphoid CelIs and Protects From Experimental Colitis - Kang, Le; Schmalzl, Angelika; Leupold, Tamara; Gonzalez-Acera, Miguel; Atreya, Raja; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Frontiers in Immunology, 2021)
A diverse spectrum of immune cells populates the intestinal mucosa reflecting the continuous stimulation by luminal antigens. In lesions of patients with inflammatory bowel disease, an aberrant inflammatory process is characterized by a very prominent infiltrate of activated immune cells producing cytokines and chemokines. These mediators perpetuate intestinal inflammation or may contribute to mucosal protection depending on the cellular context. In order to further characterize this complex immune cell network in intestinal inflammation, we investigated the contribution of the chemokine receptor CCR8 to development of colitis using a mouse model of experimental inflammation. We found that CCR8−/− mice compared to wildtype controls developed strong weight loss accompanied by increased histological and endoscopic signs of mucosal damage. Further experiments revealed that this gut protective function of CCR8 seems to be selectively mediated by the chemotactic ligand CCL1, which was particularly produced by intestinal macrophages during colitis. Moreover, we newly identified CCR8 expression on a subgroup of intestinal innate lymphoid cells producing IFN-γ and linked a functional CCL1/CCR8 axis with their abundance in the gut. Our data therefore suggest that this pathway supports tissue-specific ILC functions important for intestinal homeostasis. Modulation of this regulatory circuit may represent a new strategy to treat inflammatory bowel disease in humans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CCR8; chemokines; cytokines; inflammatory bowel disease; innate immunity; innate lymphoid cell

CD14 Plays a Protective Role in Experimental Inflammatory Bowel Disease by Enhancing Intestinal Barrier Function - Buchheister, Stephanie; Buettner, Manuela; Basic, Marijana; Noack, Andreas; Breves, Gerhard; Buchen, Barbara; Keubler, Lydia M.; Becker, Christoph; Bleich, Andre (American Journal of Pathology, 2017)
Intestinal homeostasis disturbance through intestinal barrier disruption presumably plays a key role in inflammatory bowel disease (IBD) development. Genetic and candidate gene analyses in an Il10-deficient IBD mouse model system identified Cd14 as a potentially protective candidate gene. The role of Cd14 in colitis development was determined using dextran sulfate sodium (DSS)-induced acute and an Il10-deficiency-induced chronic model of intestinal inflammation. Intestinal permeability was investigated by fluorescein isothiocyanate-dextran uptake assay, quantitative RT-PCR analysis of tight junction proteins, myosin light chain kinase, and proinflammatory cytokine expression. Immunohistological staining of occludin, Ki-67, NF-κB-p65, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling assay was performed, and intestinal inflammation severity was evaluated histologically. Untreated B6-Cd14-/- mice and wild-type controls did not differ in intestinal barrier function. However, DSS-treated Cd14-deficient and B6-Il10-/-Cd14-/- mice exhibited more severe intestinal barrier disruption, with increased histological scores and proinflammatory cytokine expression, compared to controls. Therefore, Cd14 deficiency did not influence epithelial integrity under steady-state conditions but caused intestinal barrier dysfunction under inflammation. As expected, CD14 overexpression increased barrier integrity. No difference in intestinal epithelial NF-κB translocation was observed between the investigated groups. Intestinal myosin light chain kinase expression decreased in Cd14-deficient mice under steady-state conditions and in the chronic model, whereas no difference was detected in the DSS models. Thus, CD14 plays a protective role in IBD development by enhancing intestinal barrier function.
EVALuna2:33906

Cell death inhibition by KSHV - Murtadak, Vinay; Becker, Christoph; Stürzl, Michael (Aging-Us, 2015)
EVALuna2:1975

Cell death in the gut epithelium and implications for chronic inflammation - Patankar, Jay V.; Becker, Christoph (Nature Reviews Gastroenterology & Hepatology, 2020)
The intestinal epithelium has one of the highest rates of cellular turnover in a process that is tightly regulated. As the transit-amplifying progenitors of the intestinal epithelium generate 300 cells per crypt every day, regulated cell death and sloughing at the apical surface keeps the overall cell number in check. An aberrant increase in the rate of intestinal epithelial cell (IEC) death underlies instances of extensive epithelial erosion, which is characteristic of several intestinal diseases such as inflammatory bowel disease and infectious colitis. Emerging evidence points to a crucial role of necroptosis, autophagy and pyroptosis as important modes of programmed cell death in the intestine in addition to apoptosis. The mode of cell death affects tissue restitution responses and ultimately the long-term risks of intestinal fibrosis and colorectal cancer. A vicious cycle of intestinal barrier breach, misregulated cell death and subsequent inflammation is at the heart of chronic inflammatory and infectious gastrointestinal diseases. This Review discusses the underlying molecular and cellular underpinnings that control programmed cell death in IECs, which emerge during intestinal diseases. Translational aspects of cell death modulation for the development of novel therapeutic alternatives for inflammatory bowel diseases and colorectal cancer are also discussed.
CRIS-Team Scopus Importer:2020-07-24

Cellular FLICE-like inhibitory protein secures intestinal epithelial cell survival and immune homeostasis by regulating caspase-8. - Günther, Claudia; Martini, Eva; He, Guiwei; Amann, Kerstin Ute; He, You-Wen; Neurath, Markus; Becker, Christoph; et al. (Gastroenterology, 2013)
The intestinal epithelium generates a barrier that protects mammals from potentially harmful intestinal contents, such as pathogenic bacteria. Dysregulation of epithelial cell death has been implicated in barrier dysfunction and in the pathogenesis of intestinal inflammation. We investigated mechanisms of cell-death regulation in the intestinal epithelium of mice. Conditional knockout mice (either inducible or permanent) with deletion of cellular FLICE-inhibitory protein (cFlip) or caspase-8 in the intestinal epithelium were analyzed by histology and high-resolution endoscopy. We assessed the effects of cFlip or caspase-8 deficiency on intestinal homeostasis. Expression of cFlip in the intestinal epithelium was required for constitutive activation of caspase-8 under steady-state conditions. Intestinal expression of cFlip was required for development; disruption of the gene encoding cFlip from the intestinal epithelium (cFlip(fl/fl) VillinCre(+) mice) resulted in embryonic lethality. When cFlip was deleted from the intestinal epithelium of adult mice (cFlip(iΔIEC) mice), the animals died within a few days from severe tissue destruction, epithelial cell death, and intestinal inflammation. Death of cFlip-depleted intestinal epithelial cells was regulated extrinsically and required the presence of death receptor ligands, such as tumor necrosis factor-α and CD95 ligand, but was independent of receptor-interacting protein 3. cFlip deficiency was associated with strong up-regulation of caspase-8 and caspase-3 activity and excessive apoptosis in intestinal crypts. cFlip is required for intestinal tissue homeostasis in mice. It controls the level of activation of caspase-8 to promote survival of intestinal epithelial cells. BACKGROUND & AIMS METHODS RESULTS CONCLUSIONS
Keywords: CASP8; CFLAR; Fadd; Fadd-Like Apoptosis Regulator; Fas-associated protein with death domain; IEC; NEMO; NF-κB essential modulator; Rip; TNF; TUNEL; cFLIP; cellular FLICE-like inhibitory protein; intestinal epithelial cell; receptor interacting protein; terminal deoxynucleotidyl transferase–mediated deoxyuridine triphosphate nick-end labeling; tumor necrosis factor

Chronic intestinal inflammation in mice expressing viral Flip in epithelial cells - Ruder, Barbara; Murtadak, Vinay; Stürzl, Michael; Wirtz, Stefan; Distler, Ute; Tenzer, Stefan; Mahapatro, Mousumi; Greten, Florian R.; Hu, Yinling; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; et al. (Mucosal Immunology, 2018)
Viruses are present in the intestinal microflora and are currently discussed as a potential causative mechanism for the development of inflammatory bowel disease. A number of viruses, such as Human Herpesvirus-8, express homologs to cellular FLIPs, which are major contributors for the regulation of epithelial cell death. In this study we analyzed the consequences of constitutive expression of HHV8-viral FLIP in intestinal epithelial cells (IECs) in mice. Surprisingly, expression of vFlip disrupts tissue homeostasis and induces severe intestinal inflammation. Moreover vFlipIEC-tg mice showed reduced Paneth cell numbers, associated with excessive necrotic cell death. On a molecular level vFlip expression altered classical and alternative NFκB activation. Blocking of alternative NFκB signaling by deletion of Ikka in vivo largely protected mice from inflammation and Paneth cell loss induced by vFLIP. Collectively, our data provide functional evidence that expression of a single viral protein in IECs can be sufficient to disrupt epithelial homeostasis and to initiate chronic intestinal inflammation.
EVALuna2:35131

Citrullination licenses calpain to decondense nuclei in neutrophil extracellular trap formation - Goesswein, Stefanie; Lindemann, Aylin; Mahajan, Aparna; Maueröder, Christian; Martini, Eva; Patankar, Jay; Schett, Georg; Becker, Christoph; Wirtz, Stefan; Naumann-Bartsch, Nora; Bianchi, Marco E.; Greer, Peter A.; et al. (Frontiers in Immunology, 2019)
Neutrophils respond to various stimuli by decondensing and releasing nuclear chromatin characterized by citrullinated histones as neutrophil extracellular traps (NETs). This achieves pathogen immobilization or initiation of thrombosis, yet the molecular mechanisms of NET formation remain elusive. Peptidyl arginine deiminase-4 (PAD4) achieves protein citrullination and has been intricately linked to NET formation. Here we show that citrullination represents a major regulator of proteolysis in the course of NET formation. Elevated cytosolic calcium levels trigger both peptidylarginine deiminase-4 (PAD4) and calpain activity in neutrophils resulting in nuclear decondensation typical of NETs. Interestingly, PAD4 relies on proteolysis by calpain to achieve efficient nuclear lamina breakdown and chromatin decondensation. Pharmacological or genetic inhibition of PAD4 and calpain strongly inhibit chromatin decondensation of human and murine neutrophils in response to calcium ionophores as well as the proteolysis of nuclear proteins like lamin B1 and high mobility group box protein 1 (HMGB1). Taken together, the concerted action of PAD4 and calpain induces nuclear decondensation in the course of calcium-mediated NET formation.
CRIS-Team Scopus Importer:2019-11-15
Keywords: Calpain; Cell death; Chromatin; Citrullination; Neutrophil; Nucleus; PAD4

Comparative Transcriptomics of IBD Patients Indicates Induction of Type 2 Immunity Irrespective of the Disease Ideotype - Gonzalez Acera, Miguel; Patankar, Jay; Diemand, Leonard; Siegmund, Britta; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Frontiers in Medicine, 2021)
Inflammatory cytokines initiate and sustain the perpetuation of processes leading to chronic inflammatory conditions such as inflammatory bowel diseases (IBD). The nature of the trigger causing an inflammatory reaction decides whether type 1, type 17, or type 2 immune responses, typically characterized by the respective T- helper cell subsets, come into effect. In the intestine, Type 2 responses have been linked with mucosal healing and resolution upon an immune challenge involving parasitic infections. However, type 2 cytokines are frequently elevated in certain types of IBD in particular ulcerative colitis (UC) leading to the assumption that Th2 cells might critically support the pathogenesis of UC raising the question of whether such elevated type 2 responses in IBD are beneficial or detrimental. In line with this, previous studies showed that suppression of IL-13 and other type 2 related molecules in murine models could improve the outcomes of intestinal inflammation. However, therapeutic attempts of neutralizing IL-13 in ulcerative colitis patients have yielded no benefits. Thus, a better understanding of the role of type 2 cytokines in regulating intestinal inflammation is required. Here, we took a comparative transcriptomic approach to address how Th2 responses evolve in different mouse models of colitis and human IBD datasets. Our data show that type 2 immune-related transcripts are induced in the inflamed gut of IBD patients in both Crohn's disease and UC and across widely used mouse models of IBD. Collectively our data implicate that the presence of a type 2 signature rather defines a distinct state of intestinal inflammation than a disease-specific pathomechanism.
CRIS-Team Scopus Importer:2021-06-25
Keywords: chronic inflammation; IBD; intestine; type 2 immunity; ulcerative colitis

Confocal laser endomicroscopy for in vivo diagnosis of Clostridium difficile associated colitis - a pilot study. - Günther, Claudia; Neumann, Helmut; Vieth, Michael; Mudter, Jonas; Becker, Christoph; Schoerner, Christoph; Atreya, Raja; et al. (PLoS ONE, 2013)
Clostridium difficile infection (CDI) is one of the most dreaded causes of hospital-acquired diarrhea. Main objective was to investigate whether confocal laser endomicroscopy (CLE) has the capability for in vivo diagnosis of C. difficile associated histological changes. Second objective was to prove the presence of intramucosal bacteria using CLE. 80 patients were prospectively included, 10 patients were diagnosed with CDI based on toxigenic culture. To validate the presence of intramucosal bacteria ex vivo, CLE was performed in pure C. difficile culture; additionally fluorescence in situ hybridization (FISH) was performed. Finally, CLE with fluorescence labelled oligonucleotide probe specific for C. difficile was performed ex vivo in order to prove the presence of bacteria. CLE identified CDI-associated histological changes in vivo (sensitivity and accuracy of 88.9% and 96.3%). In addition, intramucosal bacteria were visualized. The presence of these bacteria could be proven by CLE with labeled, specific molecular C. difficile probe and FISH-technique. Based on comparison between CLE and FISH analyses, sensitivity and specificity for the presence of intramucosal bacteria were 100%. CLE has the potential for in vivo diagnosis of CDI associated colitis. In addition, CLE allowed the detection of intramucosal bacteria in vivo. BACKGROUND METHODS RESULTS CONCLUSION

Cyclic derivative of morphiceptin Dmt-cyclo-(D-Lys-Phe-D-Pro-Asp)-NH2(P-317), a mixed agonist of MOP and KOP opioid receptors, exerts anti-inflammatory and anti-tumor activity in colitis and colitis-associated colorectal cancer in mice - Zielińska, Marta; Szymaszkiewicz, Agata; Jacenik, Damian; Schodel, Lena; Sałaga, Maciej; Zatorski, Hubert; Kordek, Radzisław; Becker, Christoph; Krajewska, Wanda M.; Fichna, Jakub (European Journal of Pharmacology, 2020)
Endogenous opioid system is involved in the maintenance of the intestinal homeostasis. Recently, we proved that stimulation of opioid receptors using P-317, a cyclic morphiceptin analog, resulted in the alleviation of acute colitis in mice. The aim of the current study was to assess the effect of P-317 during colitis and colitis-associated colorectal cancer in mice. Colitis was induced by addition of dextran sodium sulfate (DSS) into drinking water. Colitis-associated colorectal cancer was induced by a single intraperitoneal injection of azoxymethane (AOM) and subsequent addition of DSS into drinking water (week 2, 5, 8). During macroscopic damage evaluation the samples were collected and used for biochemical (MPO activity assay), molecular (qPCR and western blot) and histological studies. In experimental colitis, P-317 induced an anti-inflammatory response as indicated by macroscopic and microscopic scores. In the colitis-associated colorectal cancer model, a significant difference in colorectal tumor development was observed between vehicle- and P-317-treated mice. P-317 decreased the total number of colonic tumors and inhibited MPO activity. Hematoxylin and eosin staining confirmed anti-tumor activity of P-317. The expression of TNF-α was decreased in P-317-treated mice as compared to the vehicle-treated group. P-317 decreased proliferation as well as β-catenin expression in tumors. P-317, a mixed MOP and KOP receptor agonist, induced an anti-inflammatory response in experimental colitis and decreased tumor development in colitis-associated colorectal cancer in mice.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Colitis; Colitis-associated colorectal cancer; Morphiceptin; Opioid; Opioid receptor

Cytokine-Mediated Crosstalk between Immune Cells and Epithelial Cells in the Gut - Mahapatro, Mousumi; Erkert, Lena; Becker, Christoph (Cells, 2021)
Cytokines are small proteins that are secreted by a vast majority of cell types in the gut. They not only establish cell-to-cell interactions and facilitate cellular signaling, but also regulate both innate and adaptive immune responses, thereby playing a central role in genetic, inflammatory, and infectious diseases of the gut. Both, immune cells and gut epithelial cells, play important roles in intestinal disease development. The epithelium is located in between the mucosal immune system and the gut microbiome. It not only establishes an efficient barrier against gut microbes, but it also signals information from the gut lumen and its composition to the immune cell compartment. Communication across the epithelial cell layer also occurs in the other direction. Intestinal epithelial cells respond to immune cell cytokines and their response influences and shapes the microbial community within the gut lumen. Thus, the epithelium should be seen as a translator or a moderator between the microbiota and the mucosal immune system. Proper communication across the epithelium seems to be a key to gut homeostasis. Indeed, current genome-wide association studies for intestinal disorders have identified several disease susceptibility loci, which map cytokine signatures and their related signaling genes. A thorough understanding of this tightly regulated cytokine signaling network is crucial. The main objective of this review was to shed light on how cytokines can orchestrate epithelial functions such as proliferation, cell death, permeability, microbe interaction, and barrier maintenance, thereby safeguarding host health. In addition, cytokine-mediated therapy for inflammation and cancer are discussed.
CRIS-Team Scopus Importer:2021-02-05
Keywords: cytokines; gut homeostasis; IBD; immunity; inflammation; signaling

Deletion of the Casp8 gene in mice results in ileocolitis, gut barrier dysfunction, and malassimilation, which can be partially attenuated by inulin or sodium butyrate. - Günther, Claudia; Kaden-Volynets, Valentina; Zimmermann, Julia; Beisner, Julia; Becker, Christoph; Bischoff, Stephan C. (American Journal of Physiology-Gastrointestinal and Liver Physiology, 2019)
Genetic mouse models for ileocolitis are important to understand inflammatory bowel disease in humans. We examined dietetic factors that might aggravate or attenuate ileocolitis and related pathologies in such a model. Deletion of the caspase-8 gene results not only in ileocolitis but also in gut barrier dysfunction, liver steatosis, and malassimilation, which can be partially attenuated by oral inulin or sodium butyrate. Our data indicate that diet modifications can contribute to disease variability and therapy.
Keywords: caspase-8; fructose; intestinal barrier; inulin; sodium butyrate

Dietary lipids fuel GPX4-restricted enteritis resembling Crohn's disease - Mayr, Lisa; Grabherr, Felix; Schwrzler, Julian; Reitmeier, Isabelle; Sommer, Felix; Gehmacher, Thomas; Niederreiter, Lukas; He, Gui-Wei; Ruder, Barbara; Kunz, Kai T. R.; Tymoszuk, Piotr; Hilbe, Richard; et al. (Nature Communications, 2020)
The increased incidence of inflammatory bowel disease (IBD) has become a global phenomenon that could be related to adoption of a Western life-style. Westernization of dietary habits is partly characterized by enrichment with the omega-6 polyunsaturated fatty acid (PUFA) arachidonic acid (AA), which entails risk for developing IBD. Glutathione peroxidase 4 (GPX4) protects against lipid peroxidation (LPO) and cell death termed ferroptosis. We report that small intestinal epithelial cells (IECs) in Crohn's disease (CD) exhibit impaired GPX4 activity and signs of LPO. PUFAs and specifically AA trigger a cytokine response of IECs which is restricted by GPX4. While GPX4 does not control AA metabolism, cytokine production is governed by similar mechanisms as ferroptosis. A PUFA-enriched Western diet triggers focal granuloma-like neutrophilic enteritis in mice that lack one allele of Gpx4 in IECs. Our study identifies dietary PUFAs as a trigger of GPX4-restricted mucosal inflammation phenocopying aspects of human CD.
CRIS-Team WoS Importer:2020-05-12

Differential effects of ?4?7 and GPR15 on homing of effector and regulatory T cells from patients with UC to the inflamed gut in vivo - Fischer, Anika; Zundler, Sebastian; Atreya, Raja; Rath, Timo; Voskens, Caroline; Hirschmann, Simon; Lopez Posadas, Rocío; Watson, Alastair; Becker, Christoph; Schuler, Gerold; Neufert, Clemens; Atreya, Imke; et al. (Gut, 2016)
Gut homing of lymphocytes via adhesion molecules has recently emerged as new target for therapy in IBDs. We aimed to analyse the in vivo homing of effector (Teff) and regulatory (Treg) T cells to the inflamed gut via ?4?7 and G protein receptor GPR15.We assessed the expression of homing receptors on T cells in peripheral blood and inflamed mucosa. We studied the migration pattern and homing of Teff and Treg cells to the inflamed gut using intravital confocal microscopy and FACS in a humanised mouse model in dextran sodium sulfate-treated NSG (NOD.Cg-Prkdcscid-Il2rgtm1Wjl/SzJ) mice.Expression of GPR15 and ?4?7 was significantly increased on Treg rather than Teff cells in peripheral blood of patients with UC as compared with Crohn's disease and controls. In vivo analysis in a humanised mouse model showed augmented gut homing of UC Treg cells as compared with controls. Moreover, suppression of UC (but not control) Teff and Treg cell homing was noted upon treatment with the ?4?7 antibody vedolizumab. In contrast, siRNA blockade of GPR15 had only effects on homing of Teff cells but did not affect Treg homing in UC. Clinical vedolizumab treatment was associated with marked expansion of UC Treg cells in peripheral blood.?4?7 rather than GPR15 is crucial for increased colonic homing of UC Treg cells in vivo, while both receptors control UC Teff cell homing. Vedolizumab treatment impairs homing of UC Treg cells leading to their accumulation in peripheral blood with subsequent suppression of systemic Teff cell expansion.
EVALuna2:2173

Disentangling tryptophan metabolism in inflammatory bowel diseases - Becker, Christoph; Adolph, Timon Erik (Gut, 2023)
CRIS-Team WoS Importer:2023-02-03

Dynamic, transient, and robust increase in the innervation of the inflamed mucosa in inflammatory bowel diseases - Gonzalez Acera, Miguel; Bubeck, Marvin; Mascia, Fabrizio; Diemand, Leonard; Sturm, Gregor; Kuehl, Anja A.; Atreya, Raja; Lie, Dieter Chichung; Neurath, Markus; Schumann, Michael; Klose, Christoph S. N.; Trajanoski, Zlatko; et al. (Cells, 2021)
Inflammatory bowel diseases (IBD) are characterized by chronic dysregulation of immune homeostasis, epithelial demise, immune cell activation, and microbial translocation. Each of these processes leads to proinflammatory changes via the release of cytokines, damage-associated molecular patterns (DAMPs), and pathogen-associated molecular patterns (PAMPs), respectively. The impact of these noxious agents on the survival and function of the enteric nervous system (ENS) is poorly understood. Here, we show that in contrast to an expected decrease, experimental as well as clinical colitis causes an increase in the transcript levels of enteric neuronal and glial genes. Immunostaining revealed an elevated neuronal innervation of the inflamed regions of the gut mucosa. The increase was seen in models with overt damage to epithelial cells and models of T cell-induced colitis. Transcriptomic data from treatment naïve pediatric IBD patients also confirmed the increase in the neuroglial genes and were replicated on an independent adult IBD dataset. This induction in the neuroglial genes was transient as levels returned to normal upon the induction of remission in both mouse models as well as colitis patients. Our data highlight the dynamic and robust nature of the enteric nervous system in colitis and open novel questions on its regulation.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Crohn’s disease; Enteric nervous system; Inflammatory bowel diseases; Neurogenesis; Ulcerative colitis

Engineering Therapeutic Regulatory T Cells to Overexpress G Protein-Coupled Receptor 15 Improves Functional Fitness for In Vivo Gut Homing - Müller, Tanja; Liu, Lijuan; Wiesinger, Manuel; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; Diefenbach, Andreas; et al. (Gastroenterology, 2025)
CRIS-Team Scopus Importer:2025-01-31

Environmental Microbial Factors Determine the Pattern of Inflammatory Lesions in a Murine Model of Crohn's Disease-Like Inflammation - Stolzer, Iris; Kaden-Volynets, Valentina; Ruder, Barbara; Letizia, Marilena; Bittel, Miriam; Rausch, Philipp; Basic, Marijana; Bleich, André; Baines, John F.; Neurath, Markus; Wirtz, Stefan; Weidinger, Carl; et al. (Inflammatory Bowel Diseases, 2019)
Crohn's disease (CD) patients can be grouped into patients suffering from ileitis, ileocolitis, jejunoileitis, and colitis. The pathophysiological mechanism underlying this regional inflammation is still unknown. Although most murine models of inflammatory bowel disease (IBD) develop inflammation in the colon, there is an unmet need for novel models that recapitulate the spontaneous and fluctuating nature of inflammation as seen in CD. Recently, mice with an intestinal epithelial cell-specific deletion for Caspase-8 (Casp8ΔIEC mice), which are characterized by cell death-driven ileitis and disrupted Paneth cell homeostasis, have been identified as a novel model of CD-like ileitis. Here we uncovered that genetic susceptibility alone is sufficient to drive ileitis in Casp8ΔIEC mice. In sharp contrast, environmental factors, such as a disease-relevant microbial flora, determine colonic inflammation. Accordingly, depending on the microbial environment, isogenic Casp8ΔIEC mice either exclusively developed ileitis or suffered from pathologies in several parts of the gastrointestinal tract. Colitis in these mice was characterized by massive epithelial cell death, leading to spread of commensal gut microbes to the extra-intestinal space and hence an aberrant activation of the systemic immunity. We further uncovered that Casp8ΔIEC mice show qualitative and quantitative changes in the intestinal microbiome associated with an altered mucosal and systemic immune response. In summary, we identified that inflammation in this murine model of CD-like inflammation is characterized by an immune reaction, presumably directed against a disease-relevant microbiota in a genetically susceptible host, with impaired mucosal barrier function and bacterial clearance at the epithelial interface.
Keywords: Crohn’s disease; Paneth cells; cell death; colitis; ileitis; microflora

Epithelial OPA1 links mitochondrial fusion to inflammatory bowel disease - Bao, Lili; Yu, Yidong; Gonzalez Acera, Miguel; Patankar, Jay; Gießl, Andreas; Sturm, Gregor; Kühl, Anja A.; Atreya, Raja; Erkert, Lena; Gamez-Belmonte, Reyes; Krug, Susanne M.; Schmid, Benjamin; et al. (Science Translational Medicine, 2025)
Dysregulation at the intestinal epithelial barrier is a driver of inflammatory bowel disease (IBD). However, the molecular mechanisms of barrier failure are not well understood. Here, we demonstrate dysregulated mitochondrial fusion in intestinal epithelial cells (IECs) of patients with IBD and show that impaired fusion is sufficient to drive chronic intestinal inflammation. We found reduced expression of mitochondrial fusion–related genes, such as the dynamin-related guanosine triphosphatase (GTPase) optic atrophy 1 (OPA1), and fragmented mitochondrial networks in crypt IECs of patients with IBD. Mice with Opa1 deficiency in the gut epithelium (Opa1i∆IEC) spontaneously developed chronic intestinal inflammation with mucosal ulcerations and immune cell infiltration. Intestinal inflammation in Opa1i∆IEC mice was driven by microbial translocation and associated with epithelial progenitor cell death and gut barrier dysfunction. Opa1-deficient epithelial cells and human organoids exposed to a pharmacological OPA1 inhibitor showed disruption of the mitochondrial network with mitochondrial fragmentation and changes in mitochondrial size, ultrastructure, and function, resembling changes observed in patient samples. Pharmacological inhibition of the GTPase dynamin-1–like protein in organoids derived from Opa1i∆IEC mice partially reverted this phenotype. Together, our data demonstrate a role for epithelial OPA1 in regulating intestinal immune homeostasis and epithelial barrier function. Our data provide a mechanistic explanation for the observed mitochondrial dysfunction in IBD and identify mitochondrial fusion as a potential therapeutic target in this disease.
CRIS-Team Scopus Importer:2025-01-31

Epithelial presenilin-1 drives colorectal tumour growth by controlling EGFR-COX2 signalling - Gámez Belmonte, Maria de los Reyes; Mahapatro, Mousumi; Erkert, Lena; Gonzalez Acera, Miguel; Naschberger, Elisabeth; Yu, Yuqiang; Tena-Garitaonaindia, Mireia; Patankar, Jay; Wagner, Yara; Podstawa, Eva; Schoedel, Lena; Bubeck, Marvin; et al. (Gut, 2022)
Objective Psen1 was previously characterised as a crucial factor in the pathogenesis of neurodegeneration in patients with Alzheimer's disease. Little, if any, is known about its function in the gut. Here, we uncovered an unexpected functional role of Psen1 in gut epithelial cells during intestinal tumourigenesis. Design Human colorectal cancer (CRC) and control samples were investigated for PSEN1 and proteins of the gamma-secretase complex. Tumour formation was analysed in the AOM-DSS and Apc (min/+) mouse models using newly generated epithelial-specific Psen1 deficient mice. Psen1 deficient human CRC cells were studied in a xenograft tumour model. Tumour-derived organoids were analysed for growth and RNA-Seq was performed to identify Psen1-regulated pathways. Tumouroids were generated to study EGFR activation and evaluation of the influence of prostanoids. Results PSEN1 is expressed in the intestinal epithelium and its level is increased in human CRC. Psen1-deficient mice developed only small tumours and human cancer cell lines deficient in Psen1 had a reduced tumourigenicity. Tumouroids derived from Psen1-deficient Apc (min/+) mice exhibited stunted growth and reduced cell proliferation. On a molecular level, PSEN1 potentiated tumour cell proliferation via enhanced EGFR signalling and COX-2 production. Exogenous administration of PGE(2) reversed the slow growth of PSEN1 deficient tumour cells via PGE(2) receptor 4 (EP4) receptor signalling. Conclusions Psen1 drives tumour development by increasing EGFR signalling via NOTCH1 processing, and by activating the COX-2-PGE(2) pathway. PSEN1 inhibition could be a useful strategy in treatment of CRC.
CRIS-Team WoS Importer:2022-11-04
Keywords: colorectal cancer; colorectal adenomas; arachidonic and metabolism

Epithelial RAC1-dependent cytoskeleton dynamics controls cell mechanics, cell shedding and barrier integrity in intestinal inflammation - Martínez Sánchez, Luz del Carmen; Phuong Anh Ngo; Pradhan, Rashmita; Becker, Lukas S; Böhringer, David; Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Koch, Tatyana; Thonn, Veronika; Erkert, Lena; Stolzer, Iris; et al. (Gut, 2022)
Objective Increased apoptotic shedding has been linked to intestinal barrier dysfunction and development of inflammatory bowel diseases (IBD). In contrast, physiological cell shedding allows the renewal of the epithelial monolayer without compromising the barrier function. Here, we investigated the role of live cell extrusion in epithelial barrier alterations in IBD. Design Taking advantage of conditional GGTase and RAC1 knockout mice in intestinal epithelial cells (Pggt1b (i Delta IEC) and Rac1 (i Delta IEC) mice), intravital microscopy, immunostaining, mechanobiology, organoid techniques and RNA sequencing, we analysed cell shedding alterations within the intestinal epithelium. Moreover, we examined human gut tissue and intestinal organoids from patients with IBD for cell shedding alterations and RAC1 function. Results Epithelial Pggt1b deletion led to cytoskeleton rearrangement and tight junction redistribution, causing cell overcrowding due to arresting of cell shedding that finally resulted in epithelial leakage and spontaneous mucosal inflammation in the small and to a lesser extent in the large intestine. Both in vivo and in vitro studies (knockout mice, organoids) identified RAC1 as a GGTase target critically involved in prenylation-dependent cytoskeleton dynamics, cell mechanics and epithelial cell shedding. Moreover, inflamed areas of gut tissue from patients with IBD exhibited funnel-like structures, signs of arrested cell shedding and impaired RAC1 function. RAC1 inhibition in human intestinal organoids caused actin alterations compatible with arresting of cell shedding. Conclusion Impaired epithelial RAC1 function causes cell overcrowding and epithelial leakage thus inducing chronic intestinal inflammation. Epithelial RAC1 emerges as key regulator of cytoskeletal dynamics, cell mechanics and intestinal cell shedding. Modulation of RAC1 might be exploited for restoration of epithelial integrity in the gut of patients with IBD.
CRIS-Team WoS Importer:2022-03-25

E-type prostanoid receptor 4 drives resolution of intestinal inflammation by blocking epithelial necroptosis - Patankar, Jay; Muller, Tanja M.; Kantham, Srinivas; Acera, Miguel Gonzalez; Mascia, Fabrizio; Scheibe, Kristina; Mahapatro, Mousumi; Heichler, Christina; Yu, Yuqiang; Li, Wei; Ruder, Barbara; Günther, Claudia; et al. (Nature Cell Biology, 2021)
Inflammatory bowel diseases present with elevated levels of intestinal epithelial cell (IEC) death, which compromises the gut barrier, activating immune cells and triggering more IEC death. The endogenous signals that prevent IEC death and break this vicious cycle, allowing resolution of intestinal inflammation, remain largely unknown. Here we show that prostaglandin E2 signalling via the E-type prostanoid receptor 4 (EP4) on IECs represses epithelial necroptosis and induces resolution of colitis. We found that EP4 expression correlates with an improved IBD outcome and that EP4 activation induces a transcriptional signature consistent with resolution of intestinal inflammation. We further show that dysregulated necroptosis prevents resolution, and EP4 agonism suppresses necroptosis in human and mouse IECs. Mechanistically, EP4 signalling on IECs converges on receptor-interacting protein kinase 1 to suppress tumour necrosis factor-induced activation and membrane translocation of the necroptosis effector mixed-lineage kinase domain-like pseudokinase. In summary, our study indicates that EP4 promotes the resolution of colitis by suppressing IEC necroptosis.
CRIS-Team WoS Importer:2021-07-23

Expansion of T memory stem cells with superior anti-tumor immunity by Urolithin A-induced mitophagy - Denk, Dominic; Petrocelli, Valentina; Conche, Claire; Drachsler, Moritz; Ziegler, Paul K.; Braun, Angela; Kress, Alena; Nicolas, Adele M.; Mohs, Kathleen; Becker, Christoph; Neurath, Markus; Farin, Henner F.; et al. (Immunity, 2022)
T memory stem cells (TSCM) display increased self-renewal and prolonged survival capabilities, thus preventing T cell exhaustion and promoting effective anti-tumor T cell responses. TSCM cells can be expanded by Urolithin A (UA), which is produced by the commensal gut microbiome from foods rich in ellagitannins and is known to improve mitochondrial health. Oral UA administration to tumor-bearing mice conferred strong anti-tumor CD8+ T cell immunity, whereas ex vivo UA pre-treated T cells displayed improved anti-tumor function upon adoptive cell transfer. UA-induced TSCM formation depended on Pink1-mediated mitophagy triggering cytosolic release of the mitochondrial phosphatase Pgam5. Cytosolic Pgam5 dephosphorylated β-catenin, which drove Wnt signaling and compensatory mitochondrial biogenesis. Collectively, we unravel a critical signaling pathway linking mitophagy to TSCM formation and suggest that the well-tolerated metabolic compound UA represents an attractive option to improve immune therapy.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anti-tumor immunity; mitophagy; T

Externalized decondensed neutrophil chromatin occludes pancreatic ducts and drives pancreatitis - Leppkes, Moritz; Maueröder, Christian; Hirth, Sebastian; Nowecki, Stefanie; Günther, Claudia; Billmeier, Ulrike; Paulus, Susanne; Biermann, Mona; Munoz, Luis Enrique; Hoffmann, Markus; Wildner, Dane; Croxford, Andrew L.; et al. (Nature Communications, 2016)
Ductal occlusion has been postulated to precipitate focal pancreatic inflammation, while the nature of the primary occluding agents has remained elusive. Neutrophils make use of histone citrullination by peptidyl arginine deiminase-4 (PADI4) in contact to particulate agents to extrude decondensed chromatin as neutrophil extracellular traps (NETs). In high cellular density, NETs form macroscopically visible aggregates. Here we show that such aggregates form inside pancreatic ducts in humans and mice occluding pancreatic ducts and thereby driving pancreatic inflammation. Experimental models indicate that PADI4 is critical for intraductal aggregate formation and that PADI4-deficiency abrogates disease progression. Mechanistically, we identify the pancreatic juice as a strong instigator of neutrophil chromatin extrusion. Characteristic single components of pancreatic juice, such as bicarbonate ions and calcium carbonate crystals, induce aggregated NET formation. Ductal occlusion by aggregated NETs emerges as a pathomechanism with relevance in a plethora of inflammatory conditions involving secretory ducts.
EVALuna2:2052

Functional and spatial proteomics profiling reveals intra- and intercellular signaling crosstalk in colorectal cancer - Plattner, Christina; Lamberti, Giorgia; Blattmann, Peter; Kirchmair, Alexander; Rieder, Dietmar; Loncova, Zuzana; Sturm, Gregor; Scheidl, Stefan; Ijsselsteijn, Marieke; Fotakis, Georgios; Noureen, Asma; Lisandrelli, Rebecca; et al. (iScience, 2023)
Precision oncology approaches for patients with colorectal cancer (CRC) continue to lag behind other solid cancers. Functional precision oncology—a strategy that is based on perturbing primary tumor cells from cancer patients—could provide a road forward to personalize treatment. We extend this paradigm to measuring proteome activity landscapes by acquiring quantitative phosphoproteomic data from patient-derived organoids (PDOs). We show that kinase inhibitors induce inhibitor- and patient-specific off-target effects and pathway crosstalk. Reconstruction of the kinase networks revealed that the signaling rewiring is modestly affected by mutations. We show non-genetic heterogeneity of the PDOs and upregulation of stemness and differentiation genes by kinase inhibitors. Using imaging mass-cytometry-based profiling of the primary tumors, we characterize the tumor microenvironment (TME) and determine spatial heterocellular crosstalk and tumor-immune cell interactions. Collectively, we provide a framework for inferring tumor cell intrinsic signaling and external signaling from the TME to inform precision (immuno-) oncology in CRC.
CRIS-Team Scopus Importer:2023-12-01
Keywords: Cancer; Cancer systems biology; Proteomics

Functional Role of Transient Receptor Potential Channels in Immune Cells and Epithelia - Khalil, Mohammad; Alliger, Korina; Weidinger, Carl; Yerinde, Cansu; Wirtz, Stefan; Becker, Christoph; Engel, Matthias (Frontiers in Immunology, 2018)
Transient receptor potential (TRP) ion channels are widely expressed in several tissues throughout the mammalian organism. Originally, TRP channel physiology was focusing on its fundamental meaning in sensory neuronal function. Today, it is known that activation of several TRP ion channels in peptidergic neurons does not only result in neuropeptide release and consecutive neurogenic inflammation. Growing evidence demonstrates functional extra-neuronal TRP channel expression in immune and epithelial cells with important implications for mucosal immunology. TRP channels maintain intracellular calcium homeostasis to regulate various functions in the respective cells such as nociception, production and release of inflammatory mediators, phagocytosis, and cell migration. In this review, we provide an overview about TRP-mediated effects in immune and epithelial cells with an emphasis on mucosal immunology of the gut. Crosstalk between neurons, epithelial cells, and immune cells induced by activation of TRP channels orchestrates the immunologic response. Understanding of its molecular mechanisms paves the way to novel clinical approaches for the treatment of various inflammatory disorders including IBD.
EVALuna2:33883

Gp96 Peptide Antagonist gp96-II Confers Therapeutic Effects in Murine Intestinal Inflammation - Nold-Petry, Claudia A.; Nold, Marcel F.; Levy, Ofer; Kliger, Yossef; Oren, Anat; Borukhov, Itamar; Becker, Christoph; Wirtz, Stefan; Sandhu, Manjeet K.; Neurath, Markus; Dinarello, Charles A. (Frontiers in Immunology, 2017)
Background: The expression of heat shock protein gp96 is strongly correlated with the degree of tissue inflammation in ulcerative colitis and Crohn's disease, thereby leading us to the hypothesis that inhibition of expression via gp96-II peptide prevents intestinal inflammation. Methods: We employed daily injections of gp96-II peptide in two murine models of intestinal inflammation, the first resulting from five daily injections of IL-12/IL-18, the second via a single intrarectal application of TNBS (2,4,6-trinitrobenzenesulfonic acid). We also assessed the effectiveness of gp96-II peptide in murine and human primary cell culture. Results: In the IL-12/IL-18 model, all gp96-II peptide-treated animals survived until day 5, whereas 80% of placebo-injected animals died. gp96-II peptide reduced IL-12/IL-18-induced plasma IFNγ by 89%, IL-1β by 63%, IL-6 by 43% and tumor necrosis factor (TNF) by 70% compared to controls. The clinical assessment Disease Activity Index of intestinal inflammation severity was found to be significantly lower in the gp96-II-treated animals when compared to vehicle-injected mice. gp96-II peptide treatment in the TNBS model limited weight loss to 5% on day 7 compared with prednisolone treatment, whereas placebo-treated animals suffered a 20% weight loss. Histological disease severity was reduced equally by prednisolone (by 40%) and gp96-II peptide (35%). Mice treated with either gp96-II peptide or prednisolone exhibited improved endoscopic scores compared with vehicle-treated control mice: vascularity, fibrin, granularity, and translucency scores were reduced by up to 49% by prednisolone and by up to 30% by gp96-II peptide. In vitro, gp96-II peptide reduced TLR2-, TLR4- and IL-12/IL-18-induced cytokine expression in murine splenocytes, with declines in constitutive IL-6 (54%), lipopolysaccharide-induced TNF (48%), IL-6 (81%) and in Staphylococcus epidermidis-induced TNF (67%) and IL-6 (81%), as well as IL-12/IL-18-induced IFNγ (75%). gp96-II peptide reduced IL-1β, IL-6, TNF and GM-CSF in human peripheral blood mononuclear cells to a similar degree without affecting cell viability, whereas RANTES, IL-25 and MIF were twofold to threefold increased. Conclusion: gp96-II peptide protects against murine intestinal inflammation by regulating inflammation in vivo and in vitro, pointing to its promise as a novel treatment for inflammatory bowel disease.
EVALuna2:33887

Guardians of the gut: influence of the enteric nervous system on the intestinal epithelial barrier - Bubeck, Marvin; Becker, Christoph; Patankar, Jay (Frontiers in Medicine, 2023)
The intestinal mucosal surface forms one of the largest areas of the body, which is in direct contact with the environment. Co-ordinated sensory functions of immune, epithelial, and neuronal cells ensure the timely detection of noxious queues and potential pathogens and elicit proportional responses to mitigate the threats and maintain homeostasis. Such tuning and maintenance of the epithelial barrier is constantly ongoing during homeostasis and its derangement can become a gateway for systemic consequences. Although efforts in understanding the gatekeeping functions of immune cells have led the way, increasing number of studies point to a crucial role of the enteric nervous system in fine-tuning and maintaining this delicate homeostasis. The identification of immune regulatory functions of enteric neuropeptides and glial-derived factors is still in its infancy, but has already yielded several intriguing insights into their important contribution to the tight control of the mucosal barrier. In this review, we will first introduce the reader to the current understanding of the architecture of the enteric nervous system and the epithelial barrier. Next, we discuss the key discoveries and cellular pathways and mediators that have emerged as links between the enteric nervous, immune, and epithelial systems and how their coordinated actions defend against intestinal infectious and inflammatory diseases. Through this review, the readers will gain a sound understanding of the current neuro-immune-epithelial mechanisms ensuring intestinal barrier integrity and maintenance of intestinal homeostasis.
CRIS-Team Scopus Importer:2023-09-15
Keywords: enteric glia; enteric nervous system; gut epithelial barrier; inflammatory bowel disease; intrinsic primary afferent neurons

Gut Pathobiont–Derived Outer Membrane Vesicles Drive Liver Inflammation and Fibrosis in Primary Sclerosing Cholangitis–Associated Inflammatory Bowel Disease - Dorner, Heidrun; Stolzer, Iris; Mattner, Jochen; Kaminski, Sophie; Leistl, Sofia; Edrich, Lisa-Maria; Schwendner, Raphael; Hobauer, Julia; Sebald, Adrian Thomas Erwin; Leikam, Stefanie; Gonzalez Acera, Miguel; Düll, Miriam; et al. (Gastroenterology, 2024)
Background & Aims: Primary sclerosing cholangitis (PSC), often associated with inflammatory bowel disease (IBD), presents a multifactorial etiology involving genetic, immunologic, and environmental factors. Gut dysbiosis and bacterial translocation have been implicated in PSC-IBD, yet the precise mechanisms underlying their pathogenesis remain elusive. Here, we describe the role of gut pathobionts in promoting liver inflammation and fibrosis due to the release of bacterial outer membrane vesicles (OMVs). Methods: Preclinical mouse models in addition to ductal organoids were used to acquire mechanistic data. A proof-of-concept study including serum and liver biopsies of a patient cohort of PSC (n = 22), PSC-IBD (n = 45), and control individuals (n = 27) was performed to detect OMVs in the systemic circulation and liver. Results: In both preclinical model systems and in patients with PSC-IBD, the translocation of OMVs to the liver correlated with enhanced bacterial sensing and accumulation of the NLRP3 inflammasome. Using ductal organoids, we were able to precisely attribute the pro-inflammatory and pro-fibrogenic properties of OMVs to signaling pathways dependent on Toll-like receptor 4 and NLRP3–gasdermin-D. The immunostimulatory potential of OMVs could be confirmed in macrophages and hepatic stellate cells. Furthermore, when we administered gut pathobiont–derived OMVs to Mdr2–/– mice, we observed a significant enhancement in liver inflammation and fibrosis. In a translational approach, we substantiated the presence of OMVs in the systemic circulation and hepatic regions of severe fibrosis using a PSC-IBD patient cohort. Conclusions: This study demonstrates the contribution of gut pathobionts in releasing OMVs that traverse the mucosal barrier and, thus, promote liver inflammation and fibrosis in PSC-IBD. OMVs might represent a critical new environmental factor that interacts with other disease factors to cause inflammation and thus define potential new targets for fibrosis therapy.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Bacterial Extracellular Vesicle; Hepatic Inflammation; Inflammasome; PSC-IBD

Host and microbiota interactions are critical for development of murine Crohn's-like ileitis - Roulis, M.; Bongers, Gerold; Armaka, M.; Salviano, T.; He, Z.; Singh, A.; Seidler, U.; Becker, Christoph; Demengeot, Jocelyne; Furtado, G. C.; Lira, S. A.; Kollias, George (Mucosal Immunology, 2016)
Deregulation of host-microbiota interactions in the gut is a pivotal characteristic of Crohn's disease. It remains unclear, however, whether commensals and/or the dysbiotic microbiota associated with pathology in humans are causally involved in Crohn's pathogenesis. Here, we show that Crohn's-like ileitis in Tnf(?ARE/+) mice is microbiota-dependent. Germ-free Tnf(?ARE/+) mice are disease-free and the microbiota and its innate recognition through Myd88 are indispensable for tumor necrosis factor (TNF) overexpression and disease initiation in this model. The epithelium of diseased mice shows no major defects in mucus barrier and paracellular permeability. However, Tnf(?ARE/+) ileitis associates with the reduction of lysozyme-expressing Paneth cells, mediated by adaptive immune effectors. Furthermore, we show that established but not early ileitis in Tnf(?ARE/+) mice involves defective expression of antimicrobials and dysbiosis, characterized by Firmicutes expansion, including epithelial-attaching segmented filamentous bacteria, and decreased abundance of Bacteroidetes. Microbiota modulation by antibiotic treatment at an early disease stage rescues ileitis. Our results suggest that the indigenous microbiota is sufficient to drive TNF overexpression and Crohn's ileitis in the genetically susceptible Tnf(?ARE/+) hosts, whereas dysbiosis in this model results from disease-associated alterations including loss of lysozyme-expressing Paneth cells.
EVALuna2:2174

IFN-γ drives inflammatory bowel disease pathogenesis through VE-cadherin-directed vascular barrier disruption - Langer, Victoria; Vivi, Eugenia; Regensburger, Daniela; Winkler, Thomas; Waldner, Maximilian; Rath, Timo; Schmid, Benjamin; Skottke, Lisa; Lee, Somin; Jeon, Noo Li; Wohlfahrt, Thomas; Kramer, Viktoria; et al. (Journal of Clinical Investigation, 2019)
Inflammatory bowel disease (IBD) is a chronic inflammatory disorder with rising incidence. Diseased tissues are heavily vascularized. Surprisingly, the pathogenic impact of the vasculature in IBD and the underlying regulatory mechanisms remain largely unknown. IFN-γ is a major cytokine in IBD pathogenesis, but in the context of the disease, it is almost exclusively its immune-modulatory and epithelial cell-directed functions that have been considered. Recent studies by our group demonstrated that IFN-γ also exerts potent effects on blood vessels. Based on these considerations, we analyzed the vessel-directed pathogenic functions of IFN-γ and found that it drives IBD pathogenesis through vascular barrier disruption. Specifically, we show that inhibition of the IFN-γ response in vessels by endothelial-specific knockout of IFN-γ receptor 2 ameliorates experimentally induced colitis in mice. IFN-γ acts pathogenic by causing a breakdown of the vascular barrier through disruption of the adherens junction protein VE-cadherin. Notably, intestinal vascular barrier dysfunction was also confirmed in human IBD patients, supporting the clinical relevance of our findings. Treatment with imatinib restored VE-cadherin/adherens junctions, inhibited vascular permeability, and significantly reduced colonic inflammation in experimental colitis. Our findings inaugurate the pathogenic impact of IFN-γ-mediated intestinal vessel activation in IBD and open new avenues for vascular-directed treatment of this disease.

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

IL-9 and its receptor are predominantly involved in the pathogenesis of UC - Nalleweg, Nancy; Chiriac, Mircea Teodor; Podstawa, Eva; Lehmann, Christian; Rau, Tilman; Atreya, Raja; Krauss, Ekaterina; Hundorfean, Gheorghe; Fichtner-Feigl, Stefan; Hartmann, Arndt; Becker, Christoph; Mudter, Jonas (Gut, 2015)
Several pathogenic roles attributed over the past two decades to either T helper (Th)1 or Th2 cells are increasingly becoming associated with interleukin (IL)-17 and most recently IL-9 signalling. However, the implication of IL-9 in IBD has not been addressed so far.We investigated the expression of IL-9 and IL-9R by using peripheral blood, biopsies and surgical samples. We addressed the functional role of IL-9 signalling by analysis of downstream effector proteins. Using Caco-2 cell monolayers we followed the effect of IL-9 on wound healing.IL-9 mRNA expression was significantly increased in inflamed samples from patients with UC as compared with controls. CD3(+) T cells were major IL-9-expressing cells and some polymorphonuclear leucocytes (PMN) also expressed IL-9. IL-9 was co-localised with the key Th9 transcription factors interferon regulatory factor 4 and PU.1. Systemically, IL-9 was abundantly produced by activated peripheral blood lymphocytes, whereas its receptor was overexpressed on gut resident and circulating PMN. IL-9 stimulation of the latter induced IL-8 production in a dose-dependent manner and rendered PMN resistant to apoptosis suggesting a functional role for IL-9R signalling in the propagation of gut inflammation. Furthermore, IL-9R was overexpressed on gut epithelial cells and IL-9 induced STAT5 activation in these cells. Moreover, IL-9 inhibited the growth of Caco-2 epithelial cell monolayers in wound healing experiments.Our results provide evidence that IL-9 is predominantly involved in the pathogenesis of UC suggesting that targeting IL-9 might become a therapeutic option for patients with UC.
EVALuna2:1839

Immune deficiency vs. immune excess in inflammatory bowel diseases-STAT3 as a rheo-STAT of intestinal homeostasis - Leppkes, Moritz; Neurath, Markus; Herrmann, Martin; Becker, Christoph (Journal of Leukocyte Biology, 2016)
Genome-wide association studies have provided many genetic alterations, conferring susceptibility to multifactorial polygenic diseases, such as inflammatory bowel diseases. Yet, how specific genetic alterations functionally affect intestinal inflammation often remains elusive. It is noteworthy that a large overlap of genes involved in immune deficiencies with those conferring inflammatory bowel disease risk has been noted. This has provided new arguments for the debate on whether inflammatory bowel disease arises from either an excess or a deficiency in the immune system. In this review, we highlight the functional effect of an inflammatory bowel disease-risk allele, which cannot be deduced from genome-wide association studies data alone. As exemplified by the transcription factor signal transducer and activator of transcription 3 (STAT3), we show that a single gene can have a plethora of effects in various cell types of the gut. These effects may individually contribute to the restoration of intestinal homeostasis on the one hand or pave the way for excessive immunopathology on the other, as an inflammatory "rheo-STAT".
EVALuna2:1967

Immune-epithelial crosstalk at the intestinal surface - Wittkopf, Nadine; Neurath, Markus; Becker, Christoph (Journal of Gastroenterology, 2014)
The intestinal tract is one of the most complex organs of the human body. It has to exercise various functions including food and water absorption, as well as barrier and immune regulation. These functions affect not only the gut itself, but influence the overall health of the organism. Diseases involving the gastrointestinal tract such as inflammatory bowel disease and colorectal cancer therefore severely affect the patient's quality of life and can become life-threatening. Intestinal epithelial cells (IECs) play an important role in intestinal inflammation, infection, and cancer development. IECs not only constitute the first barrier in the gut against the lumen, they also constantly signal information about the gut lumen to immune cells, thereby influencing their behaviour. In contrast, by producing various antimicrobial peptides, IECs shape the microbial community within the gut. IECs also respond to cytokines and other mediators of immune cells in the lamina propria. Interactions between epithelial cells and immune cells in the intestine are responsible for gut homeostasis, and modulations of this crosstalk have been reported in studies of gut diseases. This review discusses the wide field of immune-epithelial interactions and shows the importance of immune-epithelial crosstalk in the intestine to gut homeostasis and the overall health status.
EVALuna2:1842

Immune-Epithelial Crosstalk in Inflammatory Bowel Diseases and Mucosal Wound Healing - Leppkes, Moritz; Siegmund, Britta; Becker, Christoph (Frontiers in Immunology, 2018)
EVALuna2:35168

Interferon-gamma triggers an anti-tumorigenic chain reaction in the tumor vessels of colorectal carcinoma - Stürzl, Michael; Langer, Victoria; Regensburger, Daniela; Tenkerian, Clara; Klingler, Annika; Waldner, Maximilian; Becker, Christoph; Meniel, Valerie; Grützmann, Robert; Geppert, Carol-Immanuel; Britzen-Laurent, Nathalie; Naschberger, Elisabeth (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Interferon Lambda Promotes Paneth Cell Death Via STAT1 Signaling in Mice and Is Increased in Inflamed Ileal Tissues of Patients With Crohn's Disease - Günther, Claudia; Ruder, Barbara; Stolzer, Iris; Dorner, Heidrun; He, Gui-Wei; Aden, Konrad; Strigli, Anne; Bittel, Miriam; Zeissig, Sebastian; Rosenstiel, Philip; Atreya, Raja; Neurath, Markus; et al. (Gastroenterology, 2019)
BACKGROUND & AIMS: Interferon lambda (IFNL) is expressed at high levels by intestinal epithelial cells (IECs) and mucosal immune cells in response to infection and inflammation. We investigated whether IFNL might contribute to pathogenesis of Crohn's disease (CD). METHODS: We obtained serum samples and terminal ileum biopsies from 47 patients with CD and 16 healthy individuals (controls). We measured levels of IFNL by enzyme-linked immunosorbent assay and immunohistochemistry and location of expression by confocal microscopy. Activation of IFNL signaling via STAT1 was measured in areas of no, mild, moderate, and severe inflammation and correlated with Paneth cell homeostasis and inflammation. IFNL expression and function were studied in wild-type mice and mice with intestinal epithelial cell-specific (Delta IEC) disruption or full-body disruption of specific genes (Mlkl(-/-), Stat1(Delta IEC), Casp8(Delta IEC), Casp8(Delta IEC)Ripk3(-/-), Casp8(Delta IEC)Tnfr(-/-), Casp8(Delta IEC)Mlkl(-/-), and Nod2(-/-) mice). Some mice were given tail vein injections of a vector encoding a secreted form of IFNL. Intestinal tissues were collected from mice and analyzed by immunohistochemistry and immunoblots. We generated 3-dimensional small intestinal organoids from mice and studied the effects of IFNL and inhibitors of STAT-signaling pathway. RESULTS: Patients with CD had significant increases in serum and ileal levels of IFNL compared with controls. Levels of IFNL were highest in ileum tissues with severe inflammation. High levels of IFNL associated with a reduced number of Paneth cells and increased cell death at the crypt bottom in inflamed ileum samples. Intestinal tissues from the ileum of wild-type mice injected with a vector expressing IFNL had reduced numbers of Paneth cells. IFNL-induced death of Paneth cells in mice did not occur via apoptosis, but required Mixed Lineage Kinase Domain Like (MLKL) and activation of Signal transducer and activator of transcription 1 (STAT1). In organoids, inhibitors of Janus kinase (JAK) signaling via STAT1 (glucocorticoids, tofacitinib, or filgotinib) reduced expression of proteins that mediate cell death and prevented Paneth cell death. CONCLUSIONS: Levels of IFNL are increased in serum and inflamed ileal tissues from patients with CD and associated with a loss of Paneth cells. Expression of a secreted form of IFNL in mice results in loss of Paneth cells from intestinal tissues, via STAT1 and MLKL, controlled by caspase 8. Strategies to reduce IFNL or block its effects might be developed for treatment of patients with CD affecting the terminal ileum.
Keywords: Inflammatory Bowel Diseases; Ileitis; Necroptosis; Cytokine

Interferon regulatory factor 1 (IRF-1) promotes intestinal group 3 innate lymphoid responses during Citrobacter rodentium infection - Schmalzl, Angelika; Leupold, Tamara; Kreiß, Lucas; Waldner, Maximilian; Schürmann, Sebastian; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Nature Communications, 2022)
Group 3 innate lymphoid cells (ILC3s) are crucial mediators of immunity and epithelial barrier function during immune responses against extracellular bacteria. Here, we identify Interferon regulatory factor 1 (IRF-1), a transcription factor previously associated with type 1 immunity, as an essential regulator of intestinal ILC3 accumulation and effector cytokine production. We demonstrate that IRF-1 is upregulated in the context of infection with the enteropathogen Citrobacter rodentium and that its presence is central for anatomical containment and prevention of pathogen dissemination. We furthermore show that IRF-1 is required in order for intestinal ILC3s to produce large amounts of the protective effector cytokine IL-22 early in the course of infection. On a molecular level, our data indicate that IRF-1 controls ILC3 numbers and their activation by direct transcriptional regulation of the IL-12Rβ1 chain, thereby allowing ILCs to physiologically respond to IL-23 stimulation.
CRIS-Team Scopus Importer:2022-10-14

Intestinal epithelial Gasdermin C is induced by IL-4R/STAT6 signaling but is dispensable for gut immune homeostasis - Gámez Belmonte, Maria de los Reyes; Wagner, Yara; Mahapatro, Mousumi; Wang, Ru; Erkert, Lena; Gonzalez Acera, Miguel; Cineus, Roodline; Hainbuch, Saskia; Patankar, Jay; Vöhringer, David; Hegazy, Ahmed N.; Neurath, Markus; et al. (Scientific Reports, 2024)
Gasdermin C is one of the least studied members of the gasdermin family of proteins, known for their critical involvement in pyroptosis and host defense. Furthermore, evidence for the role of Gasdermin C in the intestine is scarce and partly controversial. Here, we tested the functional role of Gasdermin C in intestinal homeostasis, inflammation and tumorigenesis. : We studied Gasdermin C in response to cytokines in intestinal organoids. We evaluated epithelial differentiation, cell death and immune infiltration under steady state conditions in a new mouse line deficient in Gasdermin C. The role of Gasdermin C was analyzed in acute colitis, infection and colitis-associated cancer. Gasdemin C is highly expressed in the intestinal epithelium and strongly induced by the type 2 cytokines IL-4 and IL-13 in a STAT6-dependent manner. Gasdermin C-deficient mice show no changes in tissue architecture and epithelial homeostasis. Epithelial organoids deficient in Gasdermin C develop normally and show no alterations in proliferation or cell death. No changes were found in models of acute colitis, type 2 intestinal infection and colitis-associated cancer. Gasdermin C genes are upregulated by type 2 immunity, yet appear dispensable for the development of intestinal inflammation, infection and colitis-associated cancer.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Gasdermin; Gut pathology; Intestinal homeostasis

Intestinal myofibroblast-specific Tpl2-Cox-2-PGE2 pathway links innate sensing to epithelial homeostasis - Roulis, Manolis; Nikolaou, Christoforos; Kotsaki, Elena; Kaffe, Eleanna; Karagianni, Niki; Koliaraki, Vasiliki; Salpea, Klelia; Ragoussis, Jiannis; Aidinis, Vassilis; Martini, Eva; Becker, Christoph; Herschman, Harvey R.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Tumor progression locus-2 (Tpl2) kinase is a major inflammatory mediator in immune cell types recently found to be genetically associated with inflammatory bowel diseases (IBDs). Here we show that Tpl2 may exert a dominant homeostatic rather than inflammatory function in the intestine mediated specifically by subepithelial intestinal myofibroblasts (IMFs). Mice with complete or IMF-specific Tpl2 ablation are highly susceptible to epithelial injury-induced colitis showing impaired compensatory proliferation in crypts and extensive ulcerations without significant changes in inflammatory responses. Following epithelial injury, IMFs sense innate or inflammatory signals and activate, via Tpl2, the cyclooxygenase-2 (Cox-2)-prostaglandin E2 (PGE2) pathway, which we show here to be essential for the epithelial homeostatic response. Exogenous PGE2 administration rescues mice with complete or IMF-specific Tpl2 ablation from defects in crypt function and susceptibility to colitis. We also show that Tpl2 expression is decreased in IMFs isolated from the inflamed ileum of IBD patients indicating that Tpl2 function in IMFs may be highly relevant to human disease. The IMF-mediated mechanism we propose also involves the IBD-associated genes IL1R1, MAPK1, and the PGE2 receptor-encoding PTGER4. Our results establish a previously unidentified myofibroblast-specific innate pathway that regulates intestinal homeostasis and may underlie IBD susceptibility in humans.
EVALuna2:1871

Investigating Intestinal Barrier Breakdown in Living Organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Naschberger, Elisabeth; Becker, Christoph; Palmisano, Ralf; Stürzl, Michael; Tripal, Philipp (Journal of Visualized Experiments, 2020)
Organoids and three-dimensional (3D) cell cultures allow the investigation of complex biological mechanisms and regulations in vitro, which previously was not possible in classical cell culture monolayers. Moreover, monolayer cell cultures are good in vitro model systems but do not represent the complex cellular differentiation processes and functions that rely on 3D structure. This has so far only been possible in animal experiments, which are laborious, time consuming, and hard to assess by optical techniques. Here we describe an assay to quantitatively determine the barrier integrity over time in living small intestinal mouse organoids. To validate our model, we applied interferon gamma (IFN-gamma) as a positive control for barrier destruction and organoids derived from IFN-gamma receptor 2 knock out mice as a negative control. The assay allowed us to determine the impact of IFN-gamma on the intestinal barrier integrity and the IFN-gamma induced degradation of the tight junction proteins claudin-2, -7, and -15. This assay could also be used to investigate the impact of chemical compounds, proteins, toxins, bacteria, or patient-derived probes on the intestinal barrier integrity.
CRIS-Team WoS Importer:2020-04-17

In vivo multi spectral colonoscopy in mice - Hohmann, Martin; Ganzleben, Ingo; Grünberg, Alexander; Menezes, Jean Gonzales; Klämpfl, Florian; Lengenfelder, Benjamin; Liebing, Eva; Heichler, Christina; Neufert, Clemens; Becker, Christoph; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2022)
Multi- and hyperspectral endoscopy are possibilities to improve the endoscopic detection of neoplastic lesions in the colon and rectum during colonoscopy. However, most studies in this context are performed on histological samples/biopsies or ex vivo. This leads to the question if previous results can be transferred to an in vivo setting. Therefore, the current study evaluated the usefulness of multispectral endoscopy in identifying neoplastic lesions in the colon. The data set consists of 25 mice with colonic neoplastic lesions and the data analysis is performed by machine learning. Another question addressed was whether adding additional spatial features based on Gauss-Laguerre polynomials leads to an improved detection rate. As a result, detection of neoplastic lesions was achieved with an MCC of 0.47. Therefore, the classification accuracy of multispectral colonoscopy is comparable with hyperspectral colonoscopy in the same spectral range when additional spatial features are used. Moreover, this paper strongly supports the current path towards the application of multi/hyperspectral endoscopy in clinical settings and shows that the challenges from transferring results from ex vivo to in vivo endoscopy can be solved.
CRIS-Team WoS Importer:2022-06-10

Know your neighbors: microbial recognition at the intestinal barrier and its implications for gut homeostasis and inflammatory bowel disease - Iyer, Krishna; Erkert, Lena; Becker, Christoph (Frontiers in Cell and Developmental Biology, 2023)
Intestinal epithelial cells (IECs) perform several physiological and metabolic functions at the epithelial barrier. IECs also play an important role in defining the overall immune functions at the mucosal region. Pattern recognition receptors (PRRs) on the cell surface and in other cellular compartments enable them to sense the presence of microbes and microbial products in the intestinal lumen. IECs are thus at the crossroads of mediating a bidirectional interaction between the microbial population and the immune cells present at the intestinal mucosa. This communication between the microbial population, the IECs and the underlying immune cells has a profound impact on the overall health of the host. In this review, we focus on the various PRRs present in different cellular compartments of IECs and discuss the recent developments in the understanding of their role in microbial recognition. Microbial recognition and signaling at the epithelial barrier have implications in the maintenance of intestinal homeostasis, epithelial barrier function, maintenance of commensals, and the overall tolerogenic function of PRRs in the gut mucosa. We also highlight the role of an aberrant microbial sensing at the epithelial barrier in the pathogenesis of inflammatory bowel disease (IBD) and the development of colorectal cancer.
CRIS-Team Scopus Importer:2023-10-20
Keywords: inflammatory bowel disease (IBD); intestinal epithelial cells (IECs); intestinal homeostasis; microbiome; mucosal immunity; pattern recognition receptors (PRRs)

Label-free analysis of inflammatory tissue remodeling in murine lung tissue based on multiphoton microscopy, Raman spectroscopy and machine learning - Kreiß, Lucas; Ganzleben, Ingo; Mühlberg, Alexander; Ritter, Paul; Schneidereit, Dominik; Becker, Christoph; Neurath, Markus; Friedrich, Oliver; Schürmann, Sebastian; Waldner, Maximilian (Journal of Biophotonics, 2022)
Inflammatory fibrotic tissue remodeling can lead to severe morbidity. Histopathology grading requires extraction of biopsies and elaborate tissue processing. Label-free optical technologies can provide diagnostic readout without preparation and artificial stainings and show potential for in vivo applications. Here, we present an integration of Raman spectroscopy (RS) and multiphoton microscopy for joint investigation of the bio-chemical composition and morphological features related to cellular components and connective tissue. Both modalities show that collagen signatures were significantly increased in a murine fibrosis model. Furthermore, autofluorescence signatures assigned to immune cells show high correlation with disease severity. RS indicates increased levels of elastin and lipids. Further, we investigated the effect of joint data sets on prediction performance in machine learning models. Although binary classification did not benefit from adding more features, multi-class classification was improved by integrated data sets.
CRIS-Team WoS Importer:2022-07-08

Lack of intestinal epithelial atg7 affects paneth cell granule formation but does not compromise immune homeostasis in the gut. - Günther, Claudia; Martini, Eva; Waldner, Maximilian; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph; et al. (Clinical & Developmental Immunology, 2012)
Genetic polymorphisms of autophagy-related genes have been associated with an increased risk to develop inflammatory bowel disease (IBD). Autophagy is an elementary process participating in several cellular events such as cellular clearance and nonapoptotic programmed cell death. Furthermore, autophagy may be involved in intestinal immune homeostasis due to its participation in the digestion of intracellular pathogens and in antigen presentation. In the present study, the role of autophagy in the intestinal epithelial layer was investigated. The intestinal epithelium is essential to maintain gut homeostasis, and defects within this barrier have been associated with the pathogenesis of IBD. Therefore, mice with intestinal epithelial deletion of Atg7 were generated and investigated in different mouse models. Knockout mice showed reduced size of granules and decreased levels of lysozyme in Paneth cells. However, this was dispensable for gut immune homeostasis and had no effect on susceptibility in mouse models of experimentally induced colitis.

Loss of IFN-gamma pathway gene expression in tumor cells as mechanism of immune escape of colorectal carcinoma - Britzen-Laurent, Nathalie; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Croner, Roland; Pilarsky, Christian; Merkel, Susanne; Stürzl, Michael (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Loss of Survivin in Intestinal Epithelial Progenitor Cells Leads to Mitotic Catastrophe and Breakdown of Gut Immune Homeostasis - Martini, Eva; Wittkopf, Nadine; Günther, Claudia; Leppkes, Moritz; Okada, Hitoshi; Watson, Alastair J.; Podstawa, Eva; Backert, Ingo; Amann, Kerstin Ute; Neurath, Markus; Becker, Christoph (Cell Reports, 2016)
A tightly regulated balance of proliferation and cell death of intestinal epithelial cells (IECs) is essential for maintenance of gut homeostasis. Survivin is highly expressed during embryogenesis and in several cancer types, but little is known about its role in adult gut tissue. Here, we show that Survivin is specifically expressed in transit-amplifying cells and Lgr5(+) stem cells. Genetic loss of Survivin in IECs resulted in destruction of intestinal integrity, mucosal inflammation, and death of the animals. Survivin deletion was associated with decreased epithelial proliferation due to defective chromosomal segregation. Moreover, Survivin-deficient animals showed induced phosphorylation of p53 and H2AX and increased levels of cell-intrinsic apoptosis in IECs. Consequently, induced deletion of Survivin in Lgr5(+) stem cells led to cell death. In summary, Survivin is a key regulator of gut tissue integrity by regulating epithelial homeostasis in the stem cell niche.
EVALuna2:2058

Matricellular Protein SPARCL1 Regulates Blood Vessel Integrity and Antagonizes Inflammatory Bowel Disease - Regensburger, Daniela; Tenkerian, Clara; Pürzer, Victoria; Schmid, Benjamin; Wohlfahrt, Thomas; Stolzer, Iris; Lopez Posadas, Rocío; Günther, Claudia; Waldner, Maximilian; Becker, Christoph; Sticht, Heinrich; Petter, Katja; et al. (Inflammatory Bowel Diseases, 2021)
Background The understanding of vascular plasticity is key to defining the role of blood vessels in physiologic and pathogenic processes. In the present study, the impact of the vascular quiescence marker SPARCL1 on angiogenesis, capillary morphogenesis, and vessel integrity was evaluated. Methods Angiogenesis was studied using the metatarsal test, an ex vivo model of sprouting angiogenesis. In addition, acute and chronic dextran sodium sulfate colitis models with SPARCL1 knockout mice were applied. Results This approach indicated that SPARCL1 inhibits angiogenesis and supports vessel morphogenesis and integrity. Evidence was provided that SPARCL1-mediated stabilization of vessel integrity counteracts vessel permeability and inflammation in acute and chronic dextran sodium sulfate colitis models. Structure-function analyses of purified SPARCL1 identified the acidic domain of the protein necessary for its anti-angiogenic activity. Conclusions Our findings inaugurate SPARCL1 as a blood vessel–derived anti-angiogenic molecule required for vessel morphogenesis and integrity. SPARCL1 opens new perspectives as a vascular marker of susceptibility to colitis and as a therapeutic molecule to support blood vessel stability in this disease. <br
Keywords: angiogenesis; blood vessel; DSS colitis; endothelial cell; inflammatory bowel disease; permeability; SPARCL1

Maximizing the diagnostic information from biopsies in chronic inflammatory bowel diseases: recommendations from the Erlangen International Consensus Conference on Inflammatory Bowel Diseases and presentation of the IBD-DCA score as a proposal for a new index for histologic activity assessment in ulcerative colitis and Crohn's disease - Lang-Schwarz, Corinna; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike I.; Hartmann, Arndt; Kamaradova, Katerina; Kuehl, Anja A.; Lauwers, Gregory Y.; et al. (Virchows Archiv, 2020)
CRIS-Team WoS Importer:2021-01-22

Ménage-à-Trois: The Ratio of Bicarbonate to CO2 and the pH Regulate the Capacity of Neutrophils to Form NETs - Maueröder, Christian; Mahajan, Aparna; Paulus, Susanne; Goesswein, Stefanie; Hahn, Jonas; Kienhoefer, Deborah; Biermann, Mona H.; Tripal, Philipp; Friedrich, Ralf P.; Munoz Becerra, Luis; Neurath, Markus; Becker, Christoph; et al. (Frontiers in Immunology, 2016)
In this study, we identified and characterized the potential of a high ratio of bicarbonate to CO2 and a moderately alkaline pH to render neutrophils prone to undergo neutrophil extracellular trap (NET) formation. Both experimental settings increased the rate of spontaneous NET release and potentiated the NET-inducing capacity of phorbol esters (phorbol-2-myristate-13-acetate), ionomycin, monosodium urate, and LPS. In contrast, an acidic environment impaired NET formation both spontaneous and induced. Our findings indicate that intracellular alkalinization of neutrophils in response to an alkaline environment leads to an increase of intracellular calcium and neutrophil activation. We further found that the anion channel blocker DIDS strongly reduced NET formation induced by bicarbonate. This finding suggests that the effects observed are due to a molecular program that renders neutrophils susceptible to NET formation. Inflammatory foci may be characterized by an acidic environment. Our data indicate that NET formation is favored by the higher pH at the border regions of inflamed areas. Moreover, our findings highlight the necessity for strict pH control during assays of NET formation.
EVALuna2:2182

Mend Your Fences: The Epithelial Barrier and its Relationship With Mucosal Immunity in Inflammatory Bowel Disease - Martini, Eva; Krug, Susanne M.; Siegmund, Britta; Neurath, Markus; Becker, Christoph (Cellular and Molecular Gastroenterology and Hepatology, 2017)
The intestinal epithelium can be easily disrupted during gut inflammation as seen in inflammatory bowel disease (IBD), such as ulcerative colitis or Crohn's disease. For a long time, research into the pathophysiology of IBD has been focused on immune cell-mediated mechanisms. Recent evidence, however, suggests that the intestinal epithelium might play a major role in the development and perpetuation of IBD. It is now clear that IBD can be triggered by disturbances in epithelial barrier integrity via dysfunctions in intestinal epithelial cell-intrinsic molecular circuits that control the homeostasis, renewal, and repair of intestinal epithelial cells. The intestinal epithelium in the healthy individual represents a semi-permeable physical barrier shielding the interior of the body from invasions of pathogens on the one hand and allowing selective passage of nutrients on the other hand. However, the intestinal epithelium must be considered much more than a simple physical barrier. Instead, the epithelium is a highly dynamic tissue that responds to a plenitude of signals including the intestinal microbiota and signals from the immune system. This epithelial response to these signals regulates barrier function, the composition of the microbiota, and mucosal immune homeostasis within the lamina propria. The epithelium can thus be regarded as a translator between the microbiota and the immune system and aberrant signal transduction between the epithelium and adjacent immune cells might promote immune dysregulation in IBD. This review summarizes the important cellular and molecular barrier components of the intestinal epithelium and emphasizes the mechanisms leading to barrier dysfunction during intestinal inflammation.
EVALuna2:35239

Murine CD83-positive T cells mediate suppressor functions in vitro and in vivo - Kreiser, Simon; Eckhardt, Jenny; Kuhnt, Christine; Stein, Marcello F.; Krzyzak, Lena; Seitz, Christine; Tucher, Christine; Knippertz, Ilka; Becker, Christoph; Günther, Claudia; Steinkasserer, Alexander; Lechmann, Matthias (Immunobiology, 2015)
The CD83 molecule (CD83) is a well-known surface marker present on mature dendritic cells (mDC). In this study, we show that CD83 is also expressed on a subset of T cells which mediate regulatory T cell (Treg)-like suppressor functions in vitro and in vivo. Treg-associated molecules including CD25, cytotoxic T lymphocyte antigen-4 (CTLA-4), glucocorticoid-induced TNFR family-related gene (GITR), Helios and neuropilin-1 (NRP-1) as well as forkhead box protein 3 (FOXP3) were specifically expressed by these CD83(+) T cells. In contrast, CD83(-) T cells showed a naive T cell phenotype with effector T cell properties upon activation. Noteworthy, CD83(-) T cells were not able to upregulate CD83 despite activation. Furthermore, CD83(+) T cells suppressed the proliferation and inflammatory cytokine release of CD83(-) T cells in vitro. Strikingly, stimulated CD83(+) T cells released soluble CD83 (sCD83), which has been reported to possess immunosuppressive properties. In vivo, using the murine transfer colitis model we could show that CD83(+) T cells were able to suppress colitis symptoms while CD83(-) T cells possessed effector functions. In addition, this CD83 expression is also conserved on expanded human Treg. Thus, from these studies we conclude that CD83(+) T cells share important features with regulatory T cells, identifying CD83 as a novel lineage marker to discriminate between different T cell populations.
EVALuna2:1841

Myenteric Plexus Immune Cell Infiltrations and Neurotransmitter Expression in Crohn’s Disease and Ulcerative Colitis - Wiese, Jakob J.; Manna, Subhakankha; Kühl, Anja A.; Fascì, Alberto; Elezkurtaj, Sefer; Sonnenberg, Elena; Bubeck, Marvin; Atreya, Raja; Becker, Christoph; Weixler, Benjamin; Siegmund, Britta; Patankar, Jay; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Pain is a cardinal symptom in inflammatory bowel disease [IBD]. An important structure in the transduction of pain signalling is the myenteric plexus [MP]. Nevertheless, IBD-associated infiltration of the MP by immune cells lacks in-depth characterisation. Herein, we decipher intra- and periganglionic immune cell infiltrations in Crohn´s disease [CD] and ulcerative colitis [UC] and provide a comparison with murine models of colitis. Methods: Full wall specimens of surgical colon resections served to examine immune cell populations by either conventional immunohistochemistry or immunofluorescence followed by either bright field or confocal microscopy. Results were compared with equivalent examinations in various murine models of intestinal inflammation. Results: Whereas the MP morphology was not significantly altered in IBD, we identified intraganglionic IBD-specific B cell- and monocyte-dominant cell infiltrations in CD. In contrast, UC-MPs were infiltrated by CD8+ T cells and revealed a higher extent of ganglionic cell apoptosis. With regard to the murine models of intestinal inflammation, the chronic dextran sulphate sodium [DSS]-induced colitis model reflected CD [and to a lesser extent UC] best, as it also showed increased monocytic infiltration as well as a modest B cell and CD8+ T cell infiltration. Conclusions: In CD, MPs were infiltrated by B cells and monocytes. In UC, mostly CD8+ cytotoxic T cells were found. The chronic DSS-induced colitis in the mouse model reflected best the MP-immune cell infiltrations representative for IBD.
CRIS-Team Scopus Importer:2024-02-16
Keywords: abdominal pain; Enteric nervous system; IBD; immune cell infiltration; inflammatory bowel disease; myenteric plexus; submucosal plexus; visceral pain

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.
Keywords: epithelial–mesenchymal transition (EMT); colorectal neoplasms; stimulated emission depletion (STED) microscopy; neutrophils; migration; extracellular traps

Neutrophils prevent rectal bleeding in ulcerative colitis by peptidyl-arginine deiminase-4-dependent immunothrombosis - Leppkes, Moritz; Lindemann, Aylin; Goesswein, Stefanie; Paulus, Susanne; Roth, Dominik; Hartung, Anne; Liebing, Eva; Zundler, Sebastian; Gonzalez-Acera, Miguel; Patankar, Jay; Mascia, Fabrizio; Scheibe, Kristina; et al. (Gut, 2021)
Objective Bleeding ulcers and erosions are hallmarks of active ulcerative colitis (UC). However, the mechanisms controlling bleeding and mucosal haemostasis remain elusive. Design We used high-resolution endoscopy and colon tissue samples of active UC (n = 36) as well as experimental models of physical and chemical mucosal damage in mice deficient for peptidyl-arginine deiminase-4 (PAD4), gnotobiotic mice and controls. We employed endoscopy, histochemistry, live-cell microscopy and flow cytometry to study eroded mucosal surfaces during mucosal haemostasis. Results Erosions and ulcerations in UC were covered by fresh blood, haematin or fibrin visible by endoscopy. Fibrin layers rather than fresh blood or haematin on erosions were inversely correlated with rectal bleeding in UC. Fibrin layers contained ample amounts of neutrophils coaggregated with neutrophil extracellular traps (NETs) with detectable activity of PAD. Transcriptome analyses showed significantly elevated PAD4 expression in active UC. In experimentally inflicted wounds, we found that neutrophils underwent NET formation in a PAD4-dependent manner hours after formation of primary blood clots, and remodelled clots to immunothrombi containing citrullinated histones, even in the absence of microbiota. PAD4-deficient mice experienced an exacerbated course of dextrane sodium sulfate-induced colitis with markedly increased rectal bleeding (96 % vs 10 %) as compared with controls. PAD4-deficient mice failed to remodel blood clots on mucosal wounds eliciting impaired healing. Thus, NET-associated immunothrombi are protective in acute colitis, while insufficient immunothrombosis is associated with rectal bleeding. Conclusion Our findings uncover that neutrophils induce secondary immunothrombosis by PAD4-dependent mechanisms. Insufficient immunothrombosis may favour rectal bleeding in UC.
CRIS-Team WoS Importer:2021-12-17

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Permeability analyses and three dimensional imaging of interferon gamma-induced barrier disintegration in intestinal organoids - Bardenbacher, Marco; Ruder, Barbara; Britzen-Laurent, Nathalie; Schmid, Benjamin; Waldner, Maximilian; Naschberger, Elisabeth; Scharl, Michael; Mueller, Werner; Günther, Claudia; Becker, Christoph; Stürzl, Michael; Tripal, Philipp (Stem Cell Research, 2019)
The aberrant regulation of the epithelial barrier integrity is involved in many diseases of the digestive tract, including inflammatory bowel diseases and colorectal cancer. Intestinal epithelial cell organoid cultures provide new perspectives for analyses of the intestinal barrier in vitro. However, established methods of barrier function analyses from two dimensional cultures have to be adjusted to the analysis of three dimensional organoid structures. Here we describe the methodology for analysis of epithelial barrier function and molecular regulation in intestinal organoids. Barrier responses to interferon-y of intestinal organoids with and without epithelial cellspecific deletion of the interferon-y-receptor 2 gene were used as a model system. The established method allowed monitoring of the kinetics of interferon-y-induced permeability changes in living organoids. Proteolytic degradation and altered localization of the tight junction proteins claudin-2, -7, and - 15 was detected using confocal spinning disc microscopy with 3D reconstruction. Hessian analysis was used for quantification of relocalization of claudins. In summary, we provide a novel methodologic approach for quantitative analyses of intestinal epithelial barrier functions in the 3D organoid model.
CRIS-Team WoS Importer:2019-03-12

PGAM5 acts as a key mediator of lung fibrosis by disrupting mitochondrial homeostasis - Ganzleben, Ingo; He, Gui-Wei; Günther, Claudia; Prigge, Elena-Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (EUROPEAN RESPIRATORY JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

PGAM5 is a key driver of mitochondrial dysfunction in experimental lung fibrosis - Ganzleben, Ingo; He, Gui Wei; Günther, Claudia; Prigge, Elena Sophie; Richter, Karsten; Rieker, Ralf; Mougiakakos, Dimitrios; Neurath, Markus; Becker, Christoph (Cellular and Molecular Life Sciences, 2019)
Rationale: Mitochondrial homeostasis has recently emerged as a focal point in the pathophysiology of idiopathic pulmonary fibrosis (IPF), but conflicting data have been reported regarding its regulation. We speculated that phosphoglycerate mutase family member 5 (PGAM5), a mitochondrial protein at the intersection of multiple cell death and mitochondrial turnover pathways, might be involved in the pathogenesis of IPF. Methods: PGAM5-deficient mice and human pulmonary epithelial cells were analyzed comparatively with PGAM5-proficient controls in a bleomycin-based model of pulmonary fibrogenesis. Mitochondria were visualized by confocal and transmission electron microscopy. Mitochondrial homeostasis was assessed using JC1 (ΔΨ) and flow cytometry. Results: PGAM5 plays an important role in pulmonary fibrogenesis. Pgam5−/− mice displayed significantly attenuated lung fibrosis compared to controls. Complementary, in vitro studies demonstrated that PGAM5 impaired mitochondrial integrity on a functional and structural level independently of mtROS-production. On a molecular level, reduced mitophagy caused by PGAM5 deficiency improved mitochondrial homeostasis. Conclusions: Our study identifies PGAM5 as an important regulator of mitochondrial homeostasis in pulmonary fibrosis. Our data further indicate PGAM5-mediated mitophagy itself as a pivotal gateway event in the mediation of self-sustaining mitochondrial damage and membrane depolarization. Our work hereby highlights the importance of mitochondrial dynamics and identifies a potential therapeutic target that warrants further studies. Graphical abstract: Toxic agents lead to mitochondrial damage resulting in depolarization of the mitochondrial membrane potential (ΔΨ) which is a gateway event for the initiation of PGAM5-mediated mitophagy. PGAM5-mediated mitophagy in turn leads to a self-perpetuating escalation of ΔΨ depolarization. Loss of the mitophagy-based damage-enhancing loop under PGAM5-deficient conditions breaks this vicious cycle, leading to improved mitochondrial homeostasis.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-06-21
Keywords: Bleomycin; IPF; Mitophagy

PGAM5-MAVS interaction regulates TBK1/ IRF3 dependent antiviral responses - Yu, Yidong; Zielinska, Marta; Li, Wei; Bernkopf, Dominic; Heilingloh, Christiane; Neurath, Markus; Becker, Christoph (Scientific Reports, 2020)
Viral infections trigger host innate immune responses, characterized by the production of type-I interferons (IFN) including IFNβ. IFNβ induces cellular antiviral defense mechanisms and thereby contributes to pathogen clearance. Accumulating evidence suggests that mitochondria constitute a crucial platform for the induction of antiviral immunity. Here we demonstrate that the mitochondrial protein phosphoglycerate mutase family member 5 (PGAM5) is important for the antiviral cellular response. Following challenge of HeLa cells with the dsRNA-analog poly(I:C), PGAM5 oligomers and high levels of PGAM5 were found in mitochondrial aggregates. Using immunoprecipitation, a direct interaction of PGAM5 with the mitochondrial antiviral-signaling protein (MAVS) was demonstrated. In addition, PGAM5 deficient cells showed diminished expression of IFNβ and IFNβ target genes as compared to WT cells. Moreover, PGAM5 deficient mouse embryonic fibroblasts (MEFs) exhibited decreased phosphorylation levels of IRF3 and TBK1 when challenged with poly(I:C) intracellularly. Finally, PGAM5 deficient MEFs, upon infection with vesicular stomatitis virus (VSV), revealed diminished IFNβ expression and increased VSV replication. Collectively, our study highlights PGAM5 as an important regulator for IFNβ production mediated via the TBK1/IRF3 signaling pathway in response to viral infection.
CRIS-Team Scopus Importer:2020-06-02

PGAM5-mediated programmed necrosis of hepatocytes drives acute liver injury - He, Gui-Wei; Günther, Claudia; Kremer, Andreas; Thonn, Veronika; Amann, Kerstin Ute; Poremba, Christopher; Neurath, Markus; Wirtz, Stefan; Becker, Christoph (Gut, 2016)
Autoimmune hepatitis (AIH) is a severe necroinflammatory liver disease associated with significant mortality. Although loss of hepatocytes is generally recognised as a key trigger of liver inflammation and liver failure, the regulation of hepatic cell death causing AIH remains poorly understood. The aim of this study was to identify molecular mechanisms that drive hepatocyte cell death in the pathogenesis of acute liver injury.Acute liver injury was modelled in mice by intravenous administration of concanavalin A (ConA). Liver injury was demonstrated by serum transaminases and histological assessment of liver sections. PGAM5-deficient mice (PGAM5-/-) were used to determine its role in experimental hepatitis. Mdivi-1 was used as an inhibitor of dynamin-related protein 1 (Drp1)-mediated mitochondrial fission. Mitochondrial fission and the expression of PGAM5 were compared between liver biopsies derived from patients with AIH and control patients.PGAM5 was highly expressed in hepatocytes of patients with AIH and in mice with ConA-induced experimental hepatitis. Deficiency of PGAM5 protected mice from ConA-induced hepatocellular death and liver injury. PGAM5 regulated ConA-induced mitochondrial fission in hepatocytes. Administration of the Drp1-inhibitor Mdivi-1 blocked mitochondrial fission, diminished hepatocyte cell death and attenuated liver tissue damage induced by ConA.Our data demonstrate for the first time that PGAM5 plays an indispensable role in the pathogenesis of ConA-induced liver injury. Downstream of PGAM5, Drp1-mediated mitochondrial fission is an obligatory step that drives the execution of hepatic necrosis and tissue damage. Our data highlight the PGAM5-Drp1 axis as a potential therapeutic target for acute immune-mediated liver injury.
EVALuna2:2219

Pleiotropic functions of TNF-? in the regulation of the intestinal epithelial response to inflammation - Leppkes, Moritz; Roulis, Manolis; Neurath, Markus; Kollias, George; Becker, Christoph (International Immunology, 2014)
An important function of intestinal epithelial cells (IECs) is to maintain the integrity of the mucosal barrier. Inflammation challenges the integrity of the mucosal barrier and the intestinal epithelium needs to adapt to a multitude of signals in order to perform the complex process of maintenance and restitution of its barrier function. Dysfunctions in epithelial barrier integrity and restoration contribute to the pathogenesis of inflammatory bowel diseases (IBDs) such as Crohn's disease and ulcerative colitis. Mucosal healing has developed to a significant treatment goal in IBD. In this review, we would like to highlight physiologic and pathologic adaptations of the intestinal epithelium to inflammation, exemplified by its responses to TNF-?. A large body of literature exists that highlights the diverse effects of this cytokine on IECs. TNF-? modulates intestinal mucus secretion and constitution. TNF-? stimulation modulates paracellular flow via tight junctional control. TNF-? induces intracellular signaling cascades that determine significant cell fate decisions such as survival, cell death or proliferation. TNF-? impacts epithelial wound healing in ErbB- and Wnt-dependent pathways while also importantly guiding immune cell attraction and function. We selected important studies from recent years with a focus on functional in vivo data providing crucial insights into the complex process of intestinal homeostasis.
EVALuna2:1867

Programming of Intestinal Epithelial Differentiation by IL-33 Derived from Pericryptal Fibroblasts in Response to Systemic Infection - Mahapatro, Mousumi; Försch, Sebastian; Hefele, Manuela; He, Gui-Wei; Giner-Ventura, Elisa; Mchedlidze, Tamar; Kindermann, Markus; Vetrano, Stefania; Danese, Silvio; Günther, Claudia; Neurath, Markus; Wirtz, Stefan; et al. (Cell Reports, 2016)
The intestinal epithelium constitutes an efficient barrier against the microbial flora. Here, we demonstrate an unexpected function of IL-33 as a regulator of epithelial barrier functions. Mice lacking IL-33 showed decreased Paneth cell numbers and lethal systemic infection in response to Salmonella typhimurium. IL-33 was produced upon microbial challenge by a distinct population of pericryptal fibroblasts neighboring the intestinal stem cell niche. IL-33 programmed the differentiation of epithelial progenitors toward secretory IEC including Paneth and goblet cells. Finally, IL-33 suppressed Notch signaling in epithelial cells and induced expression of transcription factors governing differentiation into secretory IEC. In summary, we demonstrate that gut pericryptal fibroblasts release IL-33 to translate bacterial infection into an epithelial response to promote antimicrobial defense.
EVALuna2:2065

Proteolytic Activity of the Paracaspase MALT1 Is Involved in Epithelial Restitution and Mucosal Healing - Wittner, Leonie; Wagener, Lukas; Wiese, Jakob J.; Stolzer, Iris; Krug, Susanne M.; Naschberger, Elisabeth; Jackstadt, Rene; Beyaert, Rudi; Atreya, Raja; Kühl, Anja A.; Sturm, Gregor; Gonzalez-Acera, Miguel; et al. (International Journal of Molecular Sciences, 2023)
The paracaspase MALT1 is a crucial regulator of immune responses in various cellular contexts. Recently, there is increasing evidence suggesting that MALT1 might represent a novel key player in mucosal inflammation. However, the molecular mechanisms underlying this process and the targeted cell population remain unclear. In this study, we investigate the role of MALT1 proteolytic activity in the context of mucosal inflammation. We demonstrate a significant enrichment of MALT1 gene and protein expression in colonic epithelial cells of UC patients, as well as in the context of experimental colitis. Mechanistically we demonstrate that MALT1 protease function inhibits ferroptosis, a form of iron-dependent cell death, upstream of NF-κB signaling, which can promote inflammation and tissue damage in IBD. We further show that MALT1 activity contributes to STAT3 signaling, which is essential for the regeneration of the intestinal epithelium after injury. In summary, our data strongly suggests that the protease function of MALT1 plays a critical role in the regulation of immune and inflammatory responses, as well as mucosal healing. Understanding the mechanisms by which MALT1 protease function regulates these processes may offer novel therapeutic targets for the treatment of IBD and other inflammatory diseases.
CRIS-Team Scopus Importer:2023-05-19
Keywords: ferroptosis; mucosal wound healing; ulcerative colitis

Regression of apoptosis-resistant colorectal tumors by induction of necroptosis in mice - He, Gui-Wei; Günther, Claudia; Thonn, Veronika; Yu, Yu-Qiang; Martini, Eva; Buchen, Barbara; Neurath, Markus; Stürzl, Michael; Becker, Christoph (Journal of Experimental Medicine, 2017)
Cancer cells often acquire capabilities to evade cell death induced by current chemotherapeutic treatment approaches. Caspase-8, a central initiator of death receptor-mediated apoptosis, for example, is frequently inactivated in human cancers via multiple mechanisms such as mutation. Here, we show an approach to overcome cell death resistance in caspase-8-deficient colorectal cancer (CRC) by induction of necroptosis. In both a hereditary and a xenograft mouse model of caspase-8-deficient CRC, second mitochondria-derived activator of caspase (SMAC) mimetic treatment induced massive cell death and led to regression of tumors. We further demonstrate that receptor-interacting protein kinase 3 (RIP3), which is highly expressed in mouse models of CRC and in a subset of human CRC cell lines, is the deciding factor of cancer cell susceptibility to SMAC mimetic-induced necroptosis. Thus, our data implicate that it may be worthwhile to selectively evaluate the efficacy of SMAC mimetic treatment in CRC patients with caspase-8 deficiency in clinical trials for the development of more effective personalized therapy.
EVALuna2:15307

Regulation and pathophysiological role of epithelial turnover in the gut. - Günther, Claudia; Buchen, Barbara; Neurath, Markus; Becker, Christoph (Seminars in Cell & Developmental Biology, 2014)
Cell death in the intestinal epithelium has to be tightly controlled. Excessive or misplaced epithelial cell death can result in barrier dysfunction and, as a consequence thereof, uncontrolled translocation of components of the microbial flora from the lumen into the bowel wall. Susceptibility to gastrointestinal infections or chronic inflammation of the gut, as observed in patients with inflammatory bowel disease, can be the result of such dysregulation. Conversely, defects in cell death initiation might lead to an irregular accumulation of epithelial cells and cause intestinal cancer development. Until recently, activation of caspases in the intestinal epithelium was considered as a potential contributor to barrier dysfunction and as a pathogenic factor in the development of intestinal inflammation. Thus blocking of caspases appeared to be a potential therapeutic option for patients with inflammatory bowel disease. Recent studies on necroptosis however demonstrated that also inhibition of caspases can cause barrier dysfunction and intestinal inflammation. Caspase-8 on top of its functions in the extrinsic apoptosis pathway also controls necroptosis and turns out to be an essential molecule in regulating tissue homeostasis in the gut. Epithelial caspase-8 therefore emerges as a checkpoint not only of cell survival and cell death, but also as a regulator of the mode of cell death. According to this model, both excessive activity as well as a lack of activity of caspase-8 results in epithelial cell death and intestinal inflammation and caspase-8 needs to be tightly controlled to warrant tissue homeostasis in the gut.
Keywords: Inflammation; Necroptosis; Ripoptosome

Regulation of autoantibody activity by the IL-23-TH17 axis determines the onset of autoimmune disease. - Pfeifle, René; Rothe, Tobias; Ipseiz, Natacha; Scherer, Hans U.; Culemann, Stephan; Harre, Ulrike; Ackermann, Jochen; Seefried, Martina; Kleyer, Arnd; Uderhardt, Stefan; Haugg, Benjamin; Huebert, Axel J.; et al. (Nature Immunology, 2017)
The checkpoints and mechanisms that contribute to autoantibody-driven disease are as yet incompletely understood. Here we identified the axis of interleukin 23 (IL-23) and the TH17 subset of helper T cells as a decisive factor that controlled the intrinsic inflammatory activity of autoantibodies and triggered the clinical onset of autoimmune arthritis. By instructing B cells in an IL-22- and IL-21-dependent manner, TH17 cells regulated the expression of β-galactoside α2,6-sialyltransferase 1 in newly differentiating antibody-producing cells and determined the glycosylation profile and activity of immunoglobulin G (IgG) produced by the plasma cells that subsequently emerged. Asymptomatic humans with rheumatoid arthritis (RA)-specific autoantibodies showed identical changes in the activity and glycosylation of autoreactive IgG antibodies before shifting to the inflammatory phase of RA; thus, our results identify an IL-23-TH17 cell-dependent pathway that controls autoantibody activity and unmasks a preexisting breach in immunotoleranc

RIPK1 ensures intestinal homeostasis by protecting the epithelium against apoptosis - Takahashi, Nozomi; Vereecke, Lars; Bertrand, Mathieu J. M.; Duprez, Linde; Berger, Scott B.; Divert, Tatyana; Goncalves, Amanda; Sze, Mozes; Gilbert, Barbara; Kourula, Stephanie; Goossens, Vera; Lefebvre, Sylvie; et al. (Nature, 2014)
Receptor interacting protein kinase 1 (RIPK1) has an essential role in the signalling triggered by death receptors and pattern recognition receptors. RIPK1 is believed to function as a node driving NF-?B-mediated cell survival and inflammation as well as caspase-8 (CASP8)-dependent apoptotic or RIPK3/MLKL-dependent necroptotic cell death. The physiological relevance of this dual function has remained elusive because of the perinatal death of RIPK1 full knockout mice. To circumvent this problem, we generated RIPK1 conditional knockout mice, and show that mice lacking RIPK1 in intestinal epithelial cells (IECs) spontaneously develop severe intestinal inflammation associated with IEC apoptosis leading to early death. This early lethality was rescued by antibiotic treatment, MYD88 deficiency or tumour-necrosis factor (TNF) receptor 1 deficiency, demonstrating the importance of commensal bacteria and TNF in the IEC Ripk1 knockout phenotype. CASP8 deficiency, but not RIPK3 deficiency, rescued the inflammatory phenotype completely, indicating the indispensable role of RIPK1 in suppressing CASP8-dependent apoptosis but not RIPK3-dependent necroptosis in the intestine. RIPK1 kinase-dead knock-in mice did not exhibit any sign of inflammation, suggesting that RIPK1-mediated protection resides in its kinase-independent platform function. Depletion of RIPK1 in intestinal organoid cultures sensitized them to TNF-induced apoptosis, confirming the in vivo observations. Unexpectedly, TNF-mediated NF-?B activation remained intact in these organoids. Our results demonstrate that RIPK1 is essential for survival of IECs, ensuring epithelial homeostasis by protecting the epithelium from CASP8-mediated IEC apoptosis independently of its kinase activity and NF-?B activation.
EVALuna2:1912

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Selective expression of constitutively activated STAT6 in intestinal epithelial cells promotes differentiation of secretory cells and protection against helminths - Schubart, Christoph; Krljanac, Branislav; Otte, Manuel; Symowski, Cornelia; Martini, Eva; Günther, Claudia; Becker, Christoph; Daniel, Christoph; Vöhringer, David (Mucosal Immunology, 2018)
Intestinal epithelial cells (IECs) constitute an important barrier between host and pathogen. Immune mechanisms that provide protection against gastrointestinal helminths often require IL-4Rα-induced activation of STAT6-regulated genes in IECs. However, it is not known whether STAT6 activation in IECs enhances protective immunity against helminths. Furthermore, the regulation of proliferation and differentiation processes of the intestinal epithelium by IEC-intrinsic STAT6 signaling remains unclear. To address these questions, we generated mice with specific expression of a constitutively active version of STAT6 in IECs. These VillinCre_STAT6vt mice show accumulation of secretory IECs, increased proliferation of IECs and lengthening of the small intestine. They rapidly expelled Nippostrongylus brasiliensis worms even in the absence of T cells. Furthermore, primary infection with Heligmosomoides polygyrus resulted in larval trapping in the submucosa and the fecundity of adult worms was severely impaired. Our results reveal an important IEC-intrinsic role of STAT6-regulated genes for intestinal homeostasis and protective immunity against helminths.
EVALuna2:35396

Severe Acute Respiratory Syndrome Coronavirus 2 Attachment Receptor Angiotensin-Converting Enzyme 2 Is Decreased in Crohn's Disease and Regulated By Microbial and Inflammatory Signaling - Patankar, Jay Vasant; Lehmann, Malte; Kühl, Anja A.; Atreya, Raja; Becker, Christoph; Gonzalez-Acera, Miguel; Schmitt, Heike; Gamez-Belmonte, Reyes; Mahapatro, Mousumi; Diemand, Leonard; Hartmann, Leonie; Mascia, Fabrizio; et al. (Gastroenterology, 2021)
CRIS-Team Scopus Importer:2021-02-12

SMYD2 Inhibition Downregulates TMPRSS2 and Decreases SARS-CoV-2 Infection in Human Intestinal and Airway Epithelial Cells - Yu, Yidong; Herrmann, Alexandra; Thonn, Veronika; Cordsmeier, Arne; Neurath, Markus; Enßer, Armin; Becker, Christoph (Cells, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 has lasted for more than two years. Despite the presence of very effective vaccines, the number of virus variants that escape neutralizing antibodies is growing. Thus, there is still a need for effective antiviral treatments that target virus replication independently of the circulating variant. Here, we show for the first time that deficiency or pharmacological inhibition of the cellular lysine-methyltransferase SMYD2 decreases TMPRSS2 expression on both mRNA and protein levels. SARS-CoV-2 uses TMPRSS2 for priming its spike protein to infect target cells. Treatment of cultured cells with the SMYD2 inhibitors AZ505 or BAY598 significantly inhibited viral replication. In contrast, treatment of Vero E6 cells, which do not express detectable amounts of TMPRSS2, had no effect on SARS-CoV-2 infection. Moreover, by generating a recombinant reporter virus that expresses the spike protein of the Delta variant of SARS-CoV-2, we demonstrate that BAY598 exhibits similar antiviral activity against this variant of concern. In summary, SMYD2 inhibition downregulates TMPRSS2 and blocks viral replication. Targeting cellular SMYD2 represents a promising tool to curtail SARS-CoV-2 infection.
CRIS-Team Scopus Importer:2022-04-29
Keywords: antiviral treatment; AZ505; BAY598; COVID-19; SARS-CoV-2; SMYD2; TMPRSS2

SMYD2 targets RIPK1 and restricts TNF-induced apoptosis and necroptosis to support colon tumor growth - Yu, Yidong; Thonn, Veronika; Patankar, Jay; Thoma, Oana-Maria; Waldner, Maximilian; Zielinska, Marta; Bao, Lili; Gonzalez Acera, Miguel; Wallmueller, Stefan; Engel, Felix; Stürzl, Michael; Neurath, Markus; et al. (Cell Death & Disease, 2022)
SMYD2 is a histone methyltransferase, which methylates both histone H3K4 as well as a number of non-histone proteins. Dysregulation of SMYD2 has been associated with several diseases including cancer. In the present study, we investigated whether and how SMYD2 might contribute to colorectal cancer. Increased expression levels of SMYD2 were detected in human and murine colon tumor tissues compared to tumor-free tissues. SMYD2 deficiency in colonic tumor cells strongly decreased tumor growth in two independent experimental cancer models. On a molecular level, SMYD2 deficiency sensitized colonic tumor cells to TNF-induced apoptosis and necroptosis without affecting cell proliferation. Moreover, we found that SMYD2 targeted RIPK1 and inhibited the phosphorylation of RIPK1. Finally, in a translational approach, pharmacological inhibition of SMYD2 attenuated colonic tumor growth. Collectively, our data show that SMYD2 is crucial for colon tumor growth and inhibits TNF-induced apoptosis and necroptosis.
CRIS-Team WoS Importer:2022-01-21

Soluble CD83 ameliorates experimental colitis in mice - Eckhardt, Jenny; Kreiser, Simon; Döbbeler, Marina; Nicolette, C.; Debenedette, M. A.; Tcherepanova, I. Y.; Ostalecki, Christian; Pommer, A. J.; Becker, Christoph; Günther, Claudia; Zinser, E.; Mak, T. W.; et al. (Mucosal Immunology, 2014)
The physiological balance between pro- and anti-inflammatory processes is dysregulated in inflammatory bowel diseases (IBD) as in Crohn's disease and ulcerative colitis. Conventional therapy uses anti-inflammatory and immunosuppressive corticosteroids to treat acute-phase symptoms. However, low remission rate and strong side effects of these therapies are not satisfying. Thus, there is a high medical need for new therapeutic strategies. Soluble CD83, the extracellular domain of the transmembrane CD83 molecule, has been reported to have interesting therapeutic and immunosuppressive properties by suppressing dendritic cell (DC)-mediated T-cell activation and inducing tolerogenic DCs. However, the expression and function of CD83 in IBD is still unknown. Here, we show that CD83 expression is upregulated by different leukocyte populations in a chemical-induced murine colitis model. Furthermore, in this study the potential of sCD83 to modulate colitis using an experimental murine colitis model was investigated. Strikingly, sCD83 ameliorated the clinical disease symptoms, drastically reduced mortality, and strongly decreased inflammatory cytokine expression in mesenteric lymph nodes and colon. The infiltration of macrophages and granulocytes into colonic tissues was vigorously inhibited. Mechanistically, we could show that sCD83-induced expression of indolamine 2,3-dioxygenase is essential for its protective effects.
EVALuna2:1840

Spatial Single Cell Profiling Using Imaging Mass Cytometry: Inflammatory Versus Penetrating Crohn's Disease - Lehmann, Malte; Weixler, Benjamin; Elezkurtaj, Sefer; Loddenkemper, Christopher; Atreya, Imke; Atreya, Raja; Bacher, Petra; Becker, Christoph; Bojarski, Christian; Britzen-Laurent, Nathalie; Bosch-Voskens, Caroline; Chang, Hyun Dong; et al. (Journal of Crohns & Colitis, 2024)
Background and Aims: Fistula formation is a major complication in Crohn's disease [CD] and the role of the immune cell compartment remains to be elucidated. Thus, we compared the immune cell compartment of CD fistula to inflammatory CD colitis using imaging mass cytometry [IMC] and immunofluorescence. Methods: A 36-marker panel including structural, functional, and lineage markers for use in IMC was established. This panel was applied to analyse paraffin-embedded CD fistula tract [n = 11], CD colitis [n = 10], and colon samples from non-inflamed controls [n = 12]. Computational methods for cell segmentation, dimensionality reduction, and cell type clustering were used to define cell populations for cell frequency, marker distribution, and spatial neighbourhood analysis. Multiplex immunofluorescence was used for higher resolution spatial analysis. Results: Analysis of cell frequencies in CD fistulas compared to CD colitis and control colonic samples revealed a significant increase in neutrophils, effector cytotoxic T cells, and inflammatory macrophages in CD fistula samples, whereas regulatory T cells were decreased. Neutrophils in CD fistula expressed significantly more matrix metalloproteinase 9 [MMP9], correlating with extracellular matrix remodelling. Neighbourhood analysis revealed a strong association between MMP9+ neutrophils and effector cytotoxic T cells in both CD fistulas and colitis. Conclusions: This study presents the first highly multiplexed single cell analysis of the immune cell compartment of CD fistulas and their spatial context. It links immune cell dynamics, particularly MMP9+ neutrophils, to extracellular matrix remodelling in CD fistulas, offering insights into the complex network of cellular interactions and potential therapeutic targets for CD complications.
CRIS-Team Scopus Importer:2024-09-13
Keywords: fistula; imaging mass cytometry; Penetrating Crohn's disease

STAT2 Controls Colorectal Tumorigenesis and Resistance to Anti-Cancer Drugs - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Becker, Christoph; Neurath, Markus (Cancers, 2023)
Colorectal cancer (CRC) is a significant socioeconomic burden in modern society and is accountable for millions of premature deaths each year. The role of signal transducer and activator of transcription 2 (STAT2)-dependent signaling in this context is not yet fully understood, and no therapies targeting this pathway are currently being pursued. We investigated the role of STAT2 in CRC using experimental mouse models coupled with RNA-sequencing (RNA-Seq) data and functional assays with anti-cancer agents in three-dimensional tumoroids. Stat2−/− mice showed greater resistance to the development of CRC in both inflammation-driven and inflammation-independent experimental CRC models. In ex vivo studies, tumoroids derived from Stat2−/− mice with the multiple intestinal neoplasia (Min) mutant allele of the adenomatous polyposis coli (Apc) locus exhibited delayed growth, were overall smaller and more differentiated as compared with tumoroids from ApcMin/+ wildtype (WT) mice. Notably, tumoroids from ApcMin/+ Stat2−/− mice were more susceptible to anti-cancer agents inducing cell death by different mechanisms. Our findings clearly indicated that STAT2 promotes CRC and suggested that interventions targeting STAT2-dependent signals might become an attractive therapeutic option for patients with CRC.
CRIS-Team Scopus Importer:2023-12-15
Keywords: anti-cancer therapy; Apc; colorectal cancer mouse model; STAT2; tumoroid

STAT3 Activation in Th17 and Th22 Cells Controls IL-22-Mediated Epithelial Host Defense during Infectious Colitis - Backert, Ingo; Koralov, Sergei B.; Wirtz, Stefan; Kitowski, Vera; Billmeier, Ulrike; Martini, Eva; Hofmann, Katharina; Hildner, Kai; Wittkopf, Nadine; Brecht, Katrin; Waldner, Maximilian; Rajewsky, Klaus; et al. (Journal of Immunology, 2014)
The Citrobacter rodentium model mimics the pathogenesis of infectious colitis and requires sequential contributions from different immune cell populations, including innate lymphoid cells (ILCs) and CD4(+) lymphocytes. In this study, we addressed the role of STAT3 activation in CD4(+) cells during host defense in mice against C. rodentium. In mice with defective STAT3 in CD4(+) cells (Stat3(?CD4)), the course of infection was unchanged during the innate lymphoid cell-dependent early phase, but significantly altered during the lymphocyte-dependent later phase. Stat3(?CD4) mice exhibited intestinal epithelial barrier defects, including downregulation of antimicrobial peptides, increased systemic distribution of bacteria, and prolonged reduction in the overall burden of C. rodentium infection. Immunomonitoring of lamina propria cells revealed loss of virtually all IL-22-producing CD4(+) lymphocytes, suggesting that STAT3 activation was required for IL-22 production not only in Th17 cells, but also in Th22 cells. Notably, the defective host defense against C. rodentium in Stat3(?CD4) mice could be fully restored by specific overexpression of IL-22 through a minicircle vector-based technology. Moreover, expression of a constitutive active STAT3 in CD4(+) cells shaped strong intestinal epithelial barrier function in vitro and in vivo through IL-22, and it promoted protection from enteropathogenic bacteria. Thus, our work indicates a critical role of STAT3 activation in Th17 and Th22 cells for control of the IL-22-mediated host defense, and strategies expanding STAT3-activated CD4(+) lymphocytes may be considered as future therapeutic options for improving intestinal barrier function in infectious coliti
EVALuna2:1843

Survivin is a guardian of the intestinal stem cell niche and its expression is regulated by TGF-? - Martini, Eva; Schneider, Evelyn; Neufert, Clemens; Neurath, Markus; Becker, Christoph (Cell Cycle, 2016)
As an inhibitor of apoptosis (IAP) family member, Survivin is known for its role during regulation of apoptosis. More recently its function as a cell cycle regulator has become evident. Survivin was shown to play a pivotal role during embryonic development and is highly expressed in regenerative tissue as well as in many cancer types. We examined the function of Survivin during mouse intestinal organogenesis and in gut pathophysiology. We found high expression of Survivin in experimentally induced colon cancer in mice but also in colon tumors of humans. Moreover, Survivin was regulated by TGF-? and was found to be highly expressed during mucosal healing following intestinal inflammation. We identified that expression of Survivin is essential early on in life, as specific deletion of Survivin in Villin expressing cells led to embryonic death around day 12 post coitum. Together with our recent study on the role of Survivin in the gut of adult mice our data demonstrate that Survivin is an essential guardian of embryonic gut development and adult gut homeostasis protecting the epithelium from cell death promoting the proliferation of intestinal stem and progenitor cells.
EVALuna2:2186

Systemic desensitization through TRPA1 channels by capsazepine and mustard oil - a novel strategy against inflammation and pain - Kistner, Katrin; Siklosi, Norbert; Babes, Alexandru; Khalil, Mohammad; Selescu, Tudor; Zimmermann, Katharina; Wirtz, Stefan; Becker, Christoph; Neurath, Markus; Reeh, Peter; Engel, Matthias (Scientific Reports, 2016)
We demonstrate a novel dual strategy against inflammation and pain through body-wide desensitization of nociceptors via TRPA1. Attenuation of experimental colitis by capsazepine (CPZ) has long been attributed to its antagonistic action on TRPV1 and associated inhibition of neurogenic inflammation. In contrast, we found that CPZ exerts its anti-inflammatory effects via profound desensitization of TRPA1. Micromolar CPZ induced calcium influx in isolated dorsal root ganglion (DRG) neurons from wild-type (WT) but not TRPA1-deficient mice. CPZ-induced calcium transients in human TRPA1-expressing HEK293t cells were blocked by the selective TRPA1 antagonists HC 030031 and A967079 and involved three cysteine residues in the N-terminal domain. Intriguingly, both colonic enemas and drinking water with CPZ led to profound systemic hypoalgesia in WT and TRPV1(-/-) but not TRPA1(-/-) mice. These findings may guide the development of a novel class of disease-modifying drugs with anti-inflammatory and anti-nociceptive effects.
EVALuna2:2084

Temporally Distinct Functions of the Cytokines IL-12 and IL-23 Drive Chronic Colon Inflammation in Response to Intestinal Barrier Impairment - Eftychi, Christina; Schwarzer, Robin; Vlantis, Katerina; Wachsmuth, Laurens; Basic, Marijana; Wagle, Prerana; Neurath, Markus; Becker, Christoph; Bleich, André; Pasparakis, Manolis (Immunity, 2019)
Epithelial barrier defects are implicated in the pathogenesis of inflammatory bowel disease (IBD); however, the role of microbiome dysbiosis and the cytokine networks orchestrating chronic intestinal inflammation in response to barrier impairment remain poorly understood. Here, we showed that altered Schaedler flora (ASF), a benign minimal microbiota, was sufficient to trigger colitis in a mouse model of intestinal barrier impairment. Colitis development required myeloid-cell-specific adaptor protein MyD88 signaling and was orchestrated by the cytokines IL-12, IL-23, and IFN-γ. Colon inflammation was driven by IL-12 during the early stages of the disease, but as the mice aged, the pathology shifted toward an IL-23-dependent inflammatory response driving disease chronicity. These findings reveal that IL-12 and IL-23 act in a temporally distinct, biphasic manner to induce microbiota-driven chronic intestinal inflammation. Similar mechanisms might contribute to the pathogenesis of IBD particularly in patients with underlying intestinal barrier defects.
CRIS-Team Scopus Importer:2019-08-23
Keywords: altered Schaedler flora; dysbiosis; IFN-γ; IL-12; IL-23; inflammatory bowel disease; intestinal barrier impairment; intestinal inflammation; microbiota; MyD88

Th2-dependent disappearance and phenotypic conversion of mouse alveolar macrophages - Dietschmann, Axel; Ruhl, Andreas; Murray, Peter J.; Günther, Claudia; Becker, Christoph; Fallon, Padraic; Vöhringer, David (European Journal of Immunology, 2023)
Alveolar macrophages (alvMs) play an important role for maintenance of lung function by constant removal of cellular debris in the alveolar space. They further contribute to defense against microbial or viral infections and limit tissue damage during acute lung injury. alvMs arise from embryonic progenitor cells, seed the alveoli before birth, and have life-long self-renewing capacity. However, recruited monocytes may also help to restore the alvM population after depletion caused by toxins or influenza virus infection. At present, the population dynamics and cellular plasticity of alvMs during allergic lung inflammation is poorly defined. To address this point, we used a mouse model of Aspergillus fumigatus-induced allergic lung inflammation and observed that Th2-derived IL-4 and IL-13 caused almost complete disappearance of alvMs. This effect required STAT6 expression in alvMs and also occurred in various other settings of type 2 immunity-mediated lung inflammation or administration of IL-4 complexes to the lung. In addition, Th2 cells promoted conversion of alvMs to alternatively activated macrophages and multinucleated giant cells. Given the well-established role of alvMs for maintenance of lung function, this process may have implications for resolution of inflammation and tissue homeostasis in allergic asthma.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Allergic asthma; Alternatively activated macrophages; Alveolar macrophages; Aspergillus; Multinucleated giant cells; STAT6

The Clinical Research Group 257, "CEDER" Molecular Pathogenesis and Optimized Therapy of Chronic inflammatory Bowel Diseases - Becker, Christoph; Neurath, Markus (Zeitschrift für Gastroenterologie, 2017)
EVALuna2:33814

The Intestinal Microbiota in Inflammatory Bowel Disease - Becker, Christoph; Neurath, Markus; Wirtz, Stefan (IlAR Journal, 2015)
The intestinal microbiota has important metabolic and host-protective functions. Conversely to these beneficial functions, the intestinal microbiota is thought to play a central role in the etiopathogenesis of inflammatory bowel disease (IBD; Crohn's disease and ulcerative colitis), a chronic inflammation of the gut mucosa. Genetic screens and studies in experimental mouse models have clearly demonstrated that IBD can develop due to excessive translocation of bacteria into the bowel wall or dysregulated handling of bacteria in genetically susceptible hosts. In healthy individuals, the microbiota is efficiently separated from the mucosal immune system of the gut by the gut barrier, a single layer of highly specialized epithelial cells, some of which are equipped with innate immune functions to prevent or control access of bacterial antigens to the mucosal immune cells. It is currently unclear whether the composition of the microbial flora or individual bacterial strains or pathogens induces or supports the pathogenesis of IBD. Further research will be necessary to carefully dissect the contribution of individual bacterial species to this disease and to ascertain whether specific modulation of the intestinal microbiome may represent a valuable further option for future therapeutic strategies.
EVALuna2:2000

The Microbiome in Visceral Medicine: Inflammatory Bowel Disease, Obesity and Beyond - Chiriac, Mircea T.; Mahapatro, Mousumi; Neurath, Markus; Becker, Christoph (Visceral Medicine, 2017)
It has become increasingly evident over the past two decades that the microbiota plays a nurturing role in the development of the immune system. This appears to be important since the amplitude of immune responses has a crucial regulatory function in homeostasis and the prevention of unwanted inflammation. Hence, a malfunctioning gut flora has been shown to play a key role in visceral medicine. Strong evidence demonstrates for example that intestinal inflammation can develop as a result of a dysregulated microbiota, deficient antimicrobial responses, and aberrant bacterial translocation into the bowel wall. In healthy individuals, the bacterial translocation is blocked by a single layer of highly specialized intestinal epithelial cells which forms a strong barrier that lines the gut wall. This structure is responsible for an efficient absorption of nutrients while keeping the luminal flora at bay. In susceptible individuals, for yet incompletely understood reasons, either defective epithelial barrier function or dysregulated microbial composition or microbial pathogens drive intestinal inflammation. Many therapeutic strategies focusing on the modulation of the microbiota have been proposed recently but future research including prospective human studies and gnotobiotic mouse models are still needed to evaluate the contribution and potential therapeutic value of individual bacteria to human health.
EVALuna2:35240

The pseudokinase MLKL mediates programmed hepatocellular necrosis independently of RIPK3 during hepatitis - Lopez Posadas, Rocío; Becker, Christoph; Günther, Claudia; Tenzer, Stefan; Amann, Kerstin Ute; Billmeier, Ulrike; Atreya, Raja; Fiorino, Gionata; Vetrano, Stefania; Danese, Silvio; Ekici, Arif Bülent; Wirtz, Stefan; et al. (Journal of Clinical Investigation, 2016)
Although necrosis and necroinflammation are central features of many liver diseases, the role of programmed necrosis in the context of inflammation-dependent hepatocellular death remains to be fully determined. Here, we have demonstrated that the pseudokinase mixed lineage kinase domain-like protein (MLKL), which plays a key role in the execution of receptor-interacting protein (RIP) kinase-dependent necroptosis, is upregulated and activated in human autoimmune hepatitis and in a murine model of inflammation-dependent hepatitis. Using genetic and pharmacologic approaches, we determined that hepatocellular necrosis in experimental hepatitis is driven by an MLKL-dependent pathway that occurs independently of RIPK3. Moreover, we have provided evidence that the cytotoxic activity of the proinflammatory cytokine IFN-? in hepatic inflammation is strongly connected to induction of MLKL expression via activation of the transcription factor STAT1. In summary, our results reveal a pathway for MLKL-dependent programmed necrosis that is executed in the absence of RIPK3 and potentially drives the pathogenesis of severe liver diseases.
EVALuna2:2178

The Regulation of Intestinal Inflammation and Cancer Development by Type 2 Immune Responses - Gamez-Belmonte, Reyes; Erkert, Lena; Wirtz, Stefan; Becker, Christoph (International Journal of Molecular Sciences, 2020)
The gut is among the most complex organs of the human body. It has to exert several functions including food and water absorption while setting up an efficient barrier to the outside world. Dysfunction of the gut can be life-threatening. Diseases of the gastrointestinal tract such as inflammatory bowel disease, infections, or colorectal cancer, therefore, pose substantial challenges to clinical care. The intestinal epithelium plays an important role in intestinal disease development. It not only establishes an important barrier against the gut lumen but also constantly signals information about the gut lumen and its composition to immune cells in the bowel wall. Such signaling across the epithelial barrier also occurs in the other direction. Intestinal epithelial cells respond to cytokines and other mediators of immune cells in the lamina propria and shape the microbial community within the gut by producing various antimicrobial peptides. Thus, the epithelium can be considered as an interpreter between the microbiota and the mucosal immune system, safeguarding and moderating communication to the benefit of the host. Type 2 immune responses play important roles in immune-epithelial communication. They contribute to gut tissue homeostasis and protect the host against infections with helminths. However, they are also involved in pathogenic pathways in inflammatory bowel disease and colorectal cancer. The current review provides an overview of current concepts regarding type 2 immune responses in intestinal physiology and pathophysiology.
CRIS-Team WoS Importer:2021-01-15

The Role of Programmed Necrosis in Colorectal Cancer - Yu, Yidong; Gámez Belmonte, Maria de los Reyes; Patankar, Jay; Liebing, Eva; Becker, Christoph (Cancers, 2022)
Simple Summary Necrosis is a type of cell death characterized by plasma membrane rupture and the induction of inflammation. This review focuses on colorectal cancer and outlines the role of programmed necrosis in tumor development. Potential strategies for anti-tumor treatment via targeting programmed necrosis are also discussed. For quite a long time, necrosis was considered a chaotic and unorganized form of cell death. However, studies conducted during the past few decades unveiled multiple types of programmed necrosis, such as necroptosis, pyroptosis and ferroptosis. These types of programmed necrosis have been shown to play crucial roles in mediating pathological processes, including tumorigenesis. Almost all key mediators, such as RIPK3 and MLKL in necroptosis, GSDMD and caspase 1/11 in pyroptosis and GPX4 in ferroptosis, are highly expressed in intestinal epithelial cells (IECs). An aberrant increase or decrease in programmed necrosis in IECs has been connected to intestinal disorders. Here, we review the pathways of programmed necrosis and the specific consequences of regulated necrosis in colorectal cancer (CRC) development. Translational aspects of programmed necrosis induction as a novel therapeutic alternative against CRC are also discussed.
CRIS-Team WoS Importer:2022-09-16

Topical application of Chlorin e6-PVP (Ce6-PVP) for improved endoscopic detection of neoplastic lesions in a murine colitis-associated cancer model - Ganzleben, Ingo; Hohmann, Martin; Grünberg, Alexander; Menezes, Jean Gonzales; Liebing, Eva; Günther, Claudia; Thonn, Veronika; Beß, Daniel; Becker, Christoph; Schmidt, Michael; Neurath, Markus; Waldner, Maximilian; et al. (Scientific Reports, 2020)
Screening colonoscopy is crucial in reducing the mortality of colorectal cancer. However, detecting adenomas against the backdrop of an inflamed mucosa (e.g. in ulcerative colitis) remains exceedingly difficult. Therefore, we aimed to improve neoplastic lesion detection by employing a fluorescence-based endoscopic approach. We used the well-established murine AOM/DSS model to induce inflammation-driven carcinogenesis in the colon. In our diagnostic approach, we evaluated Chlorin e6 polyvinylpyrrolidone (Ce6-PVP)-based fluorescence endoscopy in comparison to standard white-light endoscopy. A specialized pathologist then analyzed the histology of the detected lesions. Complementary in vitro studies were performed using human cell lines and a murine organoid system. Ce6-PVP-based fluorescence endoscopy had an improved detection rate of 100% (8/8) in detecting high-grade dysplasias and carcinomas over white-light detection alone with 75% (6/8). Trade-off for this superior detection rate was an increased rate of false positive lesions with an increase in the false discovery rate from 45% for white-light endoscopy to 81% for fluorescence endoscopy. We demonstrate in a proof-of-concept study that Ce6-PVP-based fluorescence endoscopy is a highly sensitive red flag technology to identify biopsy-worthy lesions in the colon.
CRIS-Team Scopus Importer:2020-08-14

Transient receptor potential melastatin 8 ion channel in macrophages modulates colitis through a balance-shift in TNF-alpha and interleukin-10 production - Khalil, Mohammad; Babes, Alexandru; Lakra, R.; Försch, Sebastian; Reeh, Peter; Wirtz, Stefan; Becker, Christoph; Neurath, Markus; Engel, Matthias (Mucosal Immunology, 2016)
The transient receptor potential (TRP) ion channel family is well characterized in sensory neurons; however, little is known about its role in the immune system. Here we show that the cold-sensing TRPM8 has an unexpected role in innate immunity. TRPM8 expression and function in macrophages were demonstrated in vitro using molecular techniques and calcium imaging. In addition, adoptive macrophage transfer and systemic interleukin (IL)-10 overexpression were performed in experimental colitis. TRPM8 activation induced calcium-transients in murine peritoneal macrophages (PM) and bone marrow-derived macrophages of wild-type (WT) but not TRPM8-deficient mice. TRPM8-deficient PM exhibited defective phagocytosis and increased motility compared with those in WT, whereas the opposite effects of TRPM8 activation were induced in WT PM. TRPM8 activation or blockage/genetic deletion induced a anti- or pro-inflammatory macrophage cytokine profile, respectively. WT mice treated with repeated menthol (TRPM8 agonist) enemas were consistently protected from experimental colitis, whereas TRPM8-deficient mice showed increased colitis susceptibility. Adoptive transfer of TRPM8-deficient macrophages aggravated colitis, whereas systemic IL-10 overexpression rescued this phenotype. TRPM8 activation in peptidergic sensory neurons did not affect neuropeptide release from the inflamed colon. TRPM8 in macrophages determines pro- or anti-inflammatory actions by regulating tumor necrosis factor-? and interleukin-10 production. These findings suggest novel TRPM8-based options for immunomodulatory intervention.
EVALuna2:2053

TRPA1 and substance P mediate colitis in mice - Engel, Matthias; Leffler, Andreas; Niedermirtl, Florian; Babes, Alexandru; Zimmermann, Katharina; Filipovic, Milos; Izydorczyk, Iwona; Eberhardt, Mirjam; Kichko, Tetyana; Müller-Tribbensee, Sonja; Khalil, Mohammad; Siklosi, Norbert; et al. (Gastroenterology, 2011)

Tumour Necrosis Factor Alpha in Intestinal Homeostasis and Gut Related Diseases - Ruder, Barbara; Atreya, Raja; Becker, Christoph (International Journal of Molecular Sciences, 2019)
The intestinal epithelium constitutes an indispensable single-layered barrier to protect the body from invading pathogens, antigens or toxins. At the same time, beneficial nutrients and water have to be absorbed by the epithelium. To prevent development of intestinal inflammation or tumour formation, intestinal homeostasis has to be tightly controlled and therefore a strict balance between cell death and proliferation has to be maintained. The proinflammatory cytokine tumour necrosis factor alpha (TNFα) was shown to play a striking role for the regulation of this balance in the gut. Depending on the cellular conditions, on the one hand TNFα is able to mediate cell survival by activating NFκB signalling. On the other hand, TNFα might trigger cell death, in particular caspase-dependent apoptosis but also caspase-independent programmed necrosis. By regulating these cell death and survival mechanisms, TNFα exerts a variety of beneficial functions in the intestine. However, TNFα signalling is also supposed to play a critical role for the pathogenesis of inflammatory bowel disease (IBD), infectious diseases, intestinal wound healing and tumour formation. Here we review the literature about the physiological and pathophysiological role of TNFα signalling for the maintenance of intestinal homeostasis and the benefits and difficulties of anti-TNFα treatment during IBD.
CRIS-Team Scopus Importer:2019-05-14
Keywords: anti-TNFα treatment; cell death; IBD; infectious disease; intestinal epithelium; tumour necrosis factor

Validation of the 'Inflammatory Bowel Disease-Distribution, Chronicity, Activity [IBD-DCA] Score' for Ulcerative Colitis and Crohn ' s Disease - Lang-Schwarz, Corinna; Angeloni, Miriam; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Dregelies, Theresa; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike; Hartmann, Arndt; Kamaradova, Katerina; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: Histological scoring plays a key role in the assessment of disease activity in ulcerative colitis [UC] and is also important in Crohns disease [CD]. Currently, there is no common scoring available for UC and CD. We aimed to validate the Inflammatory Bowel Disease [IBD]-Distribution [D], Chronicity [C], Activity [A] score [IBD-DCA score] for histological disease activity assessment in IBD.
CRIS-Team WoS Importer:2021-11-12

Viral FLIP blocks Caspase-8 driven apoptosis in the gut in vivo - Ruder, Barbara; Günther, Claudia; Stürzl, Michael; Neurath, Markus; Cesarman, Ethel; Ballon, Gianna; Becker, Christoph (PLoS ONE, 2020)
A strict cell death control in the intestinal epithelium is indispensable to maintain barrier integrity and homeostasis. In order to achieve a balance between cell proliferation and cell death, a tight regulation of Caspase-8, which is a key player in controlling apoptosis, is required. Caspase-8 activity is regulated by cellular FLIP proteins. These proteins are expressed in different isoforms (cFLIPlong and cFLIPshort) which determine cell death and survival. Interestingly, several viruses encode FLIP proteins, homologous to cFLIPshort, which are described to regulate Caspase-8 and the host cell death machinery. In the current study a mouse model was generated to show the impact of viral FLIP (vFLIP) from Kaposi's Sarcoma-associated Herpesvirus (KSHV)/ Human Herpesvirus-8 (HHV-8) on cell death regulation in the gut. Our results demonstrate that expression of vFlip in intestinal epithelial cells suppressed cFlip expression, but protected mice from lethality, tissue damage and excessive apoptotic cell death induced by genetic cFlip deletion. Finally, our model shows that vFlip expression decreases cFlip mediated Caspase-8 activation in intestinal epithelial cells. In conclusion, our data suggests that viral FLIP neutralizes and compensates for cellular FLIP, efficiently counteracting host cell death induction and facilitating further propagation in the host organism.
CRIS-Team Scopus Importer:2020-02-11

Wall of Resilience: How the Intestinal Epithelium Prevents Inflammatory Onslaught in the Gut - Liebing, Eva; Krug, Susanne M.; Neurath, Markus; Siegmund, Britta; Becker, Christoph (Cellular and Molecular Gastroenterology and Hepatology, 2025)
The intestinal epithelium forms the boundary between the intestinal immune system in the lamina propria and the outside world, the intestinal lumen, which contains a diverse array of microbial and environmental antigens. Composed of specialized cells, this epithelial monolayer has an exceptional turnover rate. Differentiated epithelial cells are released into the intestinal lumen within a few days, at the villus tip, a process that requires strict regulation. Dysfunction of the epithelial barrier increases the intestinal permeability and paves the way for luminal antigens to pass into the intestinal serosa. Stem cells at the bottom of Lieberkühn crypts provide a constant supply of mature epithelial cells. Differentiated intestinal epithelial cells exhibit a diverse array of mechanisms that enable communication with surrounding cells, fortification against microorganisms, and orchestration of nutrient absorption and hormonal balance. Furthermore, tight junctions regulate paracellular permeability properties, and their disruption can lead to an impairment of the intestinal barrier, allowing inflammation to develop or further progress. Intestinal epithelial cells provide a communication platform through which they maintain homeostasis with a spectrum of entities including immune cells, neuronal cells, and connective tissue cells. This homeostasis can be disrupted in disease, such as inflammatory bowel disease. Patients suffering from inflammatory bowel disease show an impaired gut barrier, dysregulated cellular communication, and aberrant proliferation and demise of cells. This review summarizes the individual cellular and molecular mechanisms pivotal for upholding the integrity of the intestinal epithelial barrier and shows how these can be disrupted in diseases, such as inflammatory bowel disease.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Barrier Dysfunction; Inflammatory Bowel Diseases; Intestinal Epithelium

Wheat Consumption Aggravates Colitis in Mice via Amylase Trypsin Inhibitor–mediated Dysbiosis - Pickert, Geethanjali; Wirtz, Stefan; Matzner, Johannes; Ashfaq-Khan, Muhammad; Heck, Rosario; Rosigkeit, Sebastian; Thies, Dorothe; Surabattula, Rambabu; Ehmann, Dirk; Wehkamp, Jan; Aslam, Misbah; He, Guiwei; et al. (Gastroenterology, 2020)
Background & Aims: Wheat has become the world's major staple and its consumption correlates with prevalence of noncommunicable disorders such as inflammatory bowel diseases. Amylase trypsin inhibitors (ATIs), a component of wheat, activate the intestine's innate immune response via toll-like receptor 4 (TLR4). We investigated the effects of wheat and ATIs on severity of colitis and fecal microbiota in mice. Methods: C57BL/6 wild-type and Tlr4–/– mice were fed wheat- or ATI-containing diets or a wheat-free (control) diet and then given dextran sodium sulfate to induce colitis; we also studied Il10–/– mice, which develop spontaneous colitis. Changes in fecal bacteria were assessed by taxa-specific quantitative polymerase chain reaction and 16S ribosomal RNA metagenomic sequencing. Feces were collected from mice on wheat-containing, ATI-containing, control diets and transplanted to intestines of mice with and without colitis on control or on ATI-containing diets. Intestinal tissues were collected and analyzed by histology, immunohistochemistry, and flow cytometry. Bacteria with reported immunomodulatory effects were incubated with ATIs and analyzed in radial diffusion assays. Results: The wheat- or ATI-containing diets equally increased inflammation in intestinal tissues of C57BL/6 mice with colitis, compared with mice on control diets. The ATI-containing diet promoted expansion of taxa associated with development of colitis comparable to the wheat-containing diet. ATIs inhibited proliferation of specific human commensal bacteria in radial diffusion assays. Transplantation of microbiota from feces of mice fed the wheat- or ATI-containing diets to intestines of mice on control diets increased the severity of colitis in these mice. The ATI-containing diet did not increase the severity of colitis in Tlr4–/– mice. Conclusions: Consumption of wheat or wheat ATIs increases intestinal inflammation in mice with colitis, via TLR4, and alters their fecal microbiota. Wheat-based, ATI-containing diets therefore activate TLR4 signaling and promote intestinal dysbiosis.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Inflammatory bowel diseases; microbiome; mouse model; wheat sensitivity